Method for producing polarizing film, polarizer with easy-adhesive layer, polarizing film, optical film, and image display device
By applying a boron-containing compound easily adhered composition on the surface side of the adhesive layer of the polarizing mirror, the peeling problem of polarizing film in the water resistance test and the problem of insufficient coating properties is solved, and the effect of improving water resistance and coating properties is achieved.
Patent Information
- Application Number
- CN201980080979.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-26
- Filing Date
- 2019-09-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2039-09-06
AI Technical Summary
The existing polarizing film has a peeling problem in the water resistance test after impregnation in water, and the coating property of the easily adhesive composition is insufficient, which affects production efficiency and product quality.
The adhesive composition is applied on the surface side of the adhesive layer forming the polarizing mirror. The composition of a boron-containing compound, an organic solvent having a boiling point of 85°C or higher, and a monomer having a polymerizable group is improved by later measurement coating.
The water resistance and coating properties of the polarizing film are improved, the adhesion between the polarizing mirror and the adhesive layer is enhanced, the volatility of the easily adhered composition is reduced, and the occurrence of uneven coating film thickness and adhesion is prevented.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a polarizing film having a transparent protective film disposed on at least one side of a polarizer via an adhesive layer, a polarizer with an easy-adhesion layer, and a polarizing film. The polarizing film can be used alone to form an image display device such as a liquid crystal display (LCD), an organic EL display device, a CRT, a PDP, or the like, or can be used in the form of an optical film laminated with the polarizing film to form an image display device such as a liquid crystal display (LCD), an organic EL display device, a CRT, a PDP, or the like. Background Art
[0002] Liquid crystal display devices are rapidly expanding in the market for watches, mobile phones, PDAs, notebook computers, computer monitors, DVD players, TVs, etc. Liquid crystal display devices are devices that visualize the polarization state of liquid crystal switches, and based on their display principles, polarizers are used. In particular, in applications such as TVs, high brightness, high contrast, and wide viewing angles are increasingly required, and polarizing films are increasingly required to have high transmittance, high polarization degree, and high color reproducibility.
[0003] As a polarizer, the most widely used one is an iodine-based polarizer having a structure in which iodine is adsorbed on polyvinyl alcohol (hereinafter also referred to as "PVA") and stretched, from the perspective of having high transmittance and high polarization degree. In general, a polarizing film uses a polarizing film in which a transparent protective film is bonded to both sides of the polarizer using a so-called aqueous adhesive made by dissolving a polyvinyl alcohol-based material in water (Patent Document 1 below). As the transparent protective film, triacetyl cellulose with high moisture permeability is used. When the above-mentioned aqueous adhesive is used (so-called wet lamination), a drying process is required after bonding the polarizer and the transparent protective film.
[0004] On the other hand, an active energy ray-curable adhesive has been proposed to replace the above-mentioned aqueous adhesive. When a polarizing film is manufactured using an active energy ray-curable adhesive, since a drying process is not required, the productivity of the polarizing film can be improved. For example, the present inventors have proposed a free radical polymerization type active energy ray-curable adhesive using an N-substituted amide monomer as a curable component (Patent Document 2 below).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2001-296427
[0008] Patent Document 2: Japanese Patent Application Publication No. 2012-052000 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] The adhesive layer formed using the active energy ray-curable adhesive described in Patent Document 2 can fully withstand water resistance tests such as evaluating whether there is discoloration or peeling after immersion in 60°C warm water for 6 hours. However, in recent years, adhesives for polarizing films have been required to have further improved water resistance to the extent that they can withstand more stringent water resistance tests such as evaluating whether there is peeling when the end claws are peeled off after immersion in water (saturation). Therefore, the actual situation is that there is room for further improvement in the water-resistant adhesion of polarizing films reported so far, including polarizing films using the active energy ray-curable adhesive described in Patent Document 2.
[0011] In addition, in recent years, from the viewpoints of speeding up the production process and reducing process defects, for example, when applying an easy-adhesion composition or an adhesive composition to a substrate, it is required to improve its coating property. However, the actual situation is that there is no reported example of a manufacturing method for improving the water-resistant adhesion of a polarizing film and improving its coating property when applying an easy-adhesion composition or an adhesive composition.
[0012] The present invention has been developed in view of the above-mentioned actual situation, and its purpose is to provide a method for manufacturing a polarizing film for improving the water-resistant adhesion of the polarizing film, wherein when an easy-adhesion composition is applied to the adhesive layer forming surface of the polarizer, its coating property is improved.
[0013] Another object of the present invention is to provide a polarizer with an easily adhesive layer, which is a material of a polarizing film having improved water-resistant adhesiveness, a polarizing film, an optical film, and an image display device.
[0014] Solutions to the problem
[0015] The above-mentioned problem can be solved by the following structure. That is, the present invention relates to a method for manufacturing a polarizing film, wherein the polarizing film is provided with a transparent protective film on at least one side of a polarizer via an adhesive layer, and the method includes a coating step of coating an easy-adhesion composition on the adhesive layer-forming side of the above-mentioned polarizer, wherein the above-mentioned easy-adhesion composition contains: a compound represented by the following general formula (1), and any one or both of an organic solvent having a boiling point of 85°C or higher and a monomer having a polymerizable group having a boiling point of 85°C or higher,
[0016]
[0017] (wherein, X is a functional group containing a reactive group, R 1 and R 2 Each independently represents a hydrogen atom, an aliphatic hydrocarbon group which may have a substituent, an aryl group or a heterocyclic group). It should be noted that in the present invention, the compound described in the above general formula (1) is also referred to as a "boron-containing compound".
[0018] In the method for producing a polarizing film, the compound represented by the general formula (1) is preferably a compound represented by the following general formula (1'):
[0019]
[0020] (where Y is an organic group, X, R 1 and R 2 Same meaning as above).
[0021] In the above-mentioned method for manufacturing the polarizing film, the reactive group possessed by the compound represented by the above-mentioned general formula (1) is preferably at least one reactive group selected from a (methyl)acrylamide group, an α,β-unsaturated carbonyl group, a vinyl group, a vinyl ether group, an epoxy group, an oxetane group, an amino group, an aldehyde group, a thiol group and a halogen group.
[0022] In the method for producing a polarizing film, it is preferred that the polarizer has a moisture content of 15% by weight or less.
[0023] In the method for producing a polarizing film, the easily adhesive composition preferably contains water.
[0024] In the method for producing a polarizing film, it is preferable that the coating step is a step of coating the easily adhesive composition using a post-measurement coating method.
[0025] In the method for producing a polarizing film, it is preferable that the post-measurement coating method is a gravure roll coating method using a gravure roll.
[0026] The present invention also relates to a polarizer with an easy-adhesion layer, wherein the easy-adhesion layer is formed on at least one side of the polarizer, and the easy-adhesion layer contains: a compound represented by the following general formula (1), and either or both of an organic solvent having a boiling point of 85° C. or higher and a monomer having a polymerizable group having a boiling point of 85° C. or higher.
[0027]
[0028] (wherein, X is a functional group containing a reactive group, R 1 and R 2 Each independently represents a hydrogen atom, an aliphatic hydrocarbon group which may have a substituent, an aryl group, or a heterocyclic group).
[0029] In the above-mentioned polarizer with an easy-adhesion layer, the compound represented by the above-mentioned general formula (1) is preferably a compound represented by the following general formula (1'):
[0030]
[0031] (where Y is an organic group, X, R1 and R 2 Same meaning as above).
[0032] In the above-mentioned polarizer with an easy-adhesion layer, the reactive group possessed by the compound represented by the above-mentioned general formula (1) is preferably at least one reactive group selected from a (meth)acrylamide group, an α,β-unsaturated carbonyl group, a vinyl group, a vinyl ether group, an epoxy group, an oxetanyl group, an amino group, an aldehyde group, a mercapto group, and a halogen group.
[0033] In addition, the present invention relates to a polarizing film, an optical film, and an image display device, wherein the polarizing film is provided with a transparent protective film via an adhesive layer on the easy-bonding layer forming surface of the polarizer with an easy-bonding layer as described in any of the above items, the above optical film is stacked with at least one sheet of the above polarizing film, and the above image display device uses the above-described polarizing film and / or the above-described optical film.
[0034] Effects of the Invention
[0035] In the manufacturing method of the polarizing film of the present invention, there is a coating step of coating an easy-adhesive composition on the adhesive layer forming surface side of the polarizer to improve the water-resistant adhesion of the polarizing film. As a method for setting an easy-adhesive layer on the polarizer, in the past, an easy-adhesive composition was generally coated on the polarizer, and the easy-adhesive composition was mixed with various resins such as polyester skeletons, polyether skeletons, polycarbonate skeletons, polyurethane skeletons, silicones, polyamide skeletons, polyimide skeletons, polyvinyl alcohol skeletons, etc., and low-boiling point organic solvents such as isopropyl alcohol and water were mixed as diluents in consideration of drying and handling properties. However, in the existing method, it is sometimes difficult to control the drying time of the low-boiling point organic solvent and water mixed as diluents, and the timing cannot be optimized. In this case, due to the deterioration of the smoothness of the coating surface, or the deterioration of the peeling property of the polarizer and the coating member of the coating device, the coating property of the easy-adhesive composition is sometimes deteriorated.
[0036] However, in the present invention, the boron-containing compound described in the above formula (1) is mixed with either or both of an organic solvent having a boiling point of 85°C or higher and a monomer having a polymerizable group having a boiling point of 85°C or higher in the easy-adhesion composition. This can improve the water-resistant adhesion of the polarizing film and improve the coating properties of the easy-adhesion composition when it is applied to the adhesive layer forming surface of the polarizer.
[0037] In the easy-adhesive composition, the boron-containing compound described in the above formula (1) can react with the functional groups such as hydroxyl groups possessed by the polarizer, thereby improving the adhesion between the polarizer and the adhesive layer, and as a result, the effect of improving the water-resistant adhesion of the polarizing film can be exerted. Among them, when the moisture content of the polarizer is low, specifically, for example, when the moisture content of the polarizer is less than 15% by weight, there is a case where the boron-containing compound and the functional groups possessed by the polarizer cannot fully react and the above-mentioned effect cannot be fully obtained. However, even when the moisture content of the polarizer is low, by adding water to the easy-adhesive composition, the reactivity of the boron-containing compound to the functional groups possessed by the polarizer can be improved, thereby improving the adhesion between the polarizer and the adhesive layer. As a result, even when the moisture content of the polarizer is low, it is possible to take into account both the improvement of the water-resistant adhesion of the polarizing film and the improvement of the coating property when the easy-adhesive composition is applied to the adhesive layer forming surface of the polarizer.
[0038] For the method for manufacturing the polarizing film of the present invention, when the coating process is a process of applying the above-mentioned easy-adhesion composition by a post-measurement coating method, the water-resistant adhesion of the polarizing film can be improved, and the coating property when the easy-adhesion composition is applied to the adhesive layer forming surface of the polarizer can be particularly improved. It should be noted that in the present invention, the "post-measurement coating method" refers to a method of applying an external force to the liquid film to remove excess liquid, thereby obtaining a given coating film thickness. As specific examples of the post-measurement coating method, a gravure roller coating method, a forward roller coating method, an air knife coating method, a rod / rod coating method, etc. can be cited. In the present invention, when the coating process is a process of applying the above-mentioned easy-adhesion composition by a post-measurement coating method, the reason for obtaining the above-mentioned effect can be inferred as described below.
[0039] In the post-measurement coating method, an external force is applied to the liquid film of the easy-adhesive composition after coating, so the easy-adhesive composition becomes easy to volatilize. As a result, the following undesirable situations may occur: when removing excess liquid in order to obtain a given coating film thickness, the easy-adhesive composition volatilizes more than necessary, and the coating film thickness becomes uneven (this phenomenon is also referred to as "lateral unevenness"); or the coating film exhibits adhesion due to the volatilization of the easy-adhesive composition, and the coating film of the easy-adhesive composition exhibits adhesion to the coating member of the coating device used in the post-measurement coating method, such as the gravure roller in the gravure roller coating method, and the peelability of the polarizer as the coating object and the gravure roller is deteriorated (this phenomenon is also referred to as "adhesion"). However, in the present invention, the boron-containing compound described in the above formula (1) and at least one selected from an organic solvent having a boiling point of 85°C or more and a monomer having a polymerizable group are simultaneously formulated in the easy-adhesive composition. Thus, the boron-containing compound can improve the adhesion between the polarizer and the adhesive layer, reduce the volatilization of the easy-adhesive composition, and prevent the occurrence of lateral unevenness and adhesion. As a result, in the method for manufacturing the polarizing film of the present invention, when the coating step is a step of coating the easy-adhesive composition by a post-measurement coating method, the water-resistant adhesion of the polarizing film can be improved, and the coating property when the easy-adhesive composition is coated on the adhesive layer forming surface of the polarizer can be particularly improved.
[0040] In the polarizer with easy-adhesion layer of the present invention, the easy-adhesion layer contains a boron-containing compound, an organic solvent with a boiling point of 85°C or more, and a monomer with a polymerizable group with a boiling point of 85°C or more, or both thereof. Therefore, the polarizing film and the optical film having the above-mentioned polarizer with easy-adhesion layer have excellent improved water-resistant adhesion. Therefore, the image display device using the polarizing film and / or optical film of the present invention is particularly useful in applications requiring water-resistant adhesion. DETAILED DESCRIPTION
[0041] The present invention relates to a method for producing a polarizing film having a transparent protective film provided on at least one surface of a polarizer via an adhesive layer, the method comprising a coating step of coating an easily adhesive composition on the adhesive layer-formed surface of the polarizer.
[0042] <Easy-adhesion composition>
[0043] In the present invention, the easy-adhesion composition contains a compound represented by the following general formula (1):
[0044] [Chemical formula 5]
[0045]
[0046] (wherein, X is a functional group containing a reactive group, R 1 and R2 Each independently represents a hydrogen atom, an aliphatic hydrocarbon group which may have a substituent, an aryl group or a heterocyclic group). Examples of the aliphatic hydrocarbon group include a linear or branched alkyl group having 1 to 20 carbon atoms which may have a substituent, a cyclic alkyl group having 3 to 20 carbon atoms which may have a substituent, and an alkenyl group having 2 to 20 carbon atoms. Examples of the aryl group include a phenyl group having 6 to 20 carbon atoms which may have a substituent, a naphthyl group having 10 to 20 carbon atoms which may have a substituent, and the like. Examples of the heterocyclic group include a 5-membered ring or a 6-membered ring group which contains at least one heteroatom and may have a substituent. They may be linked to each other to form a ring. In the general formula (1), R 1 and R 2 , preferably a hydrogen atom, a straight-chain or branched alkyl group having 1 to 3 carbon atoms, and most preferably a hydrogen atom. It should be noted that in the polarizing film finally manufactured, the compound represented by the general formula (1) may be present in the easy-adhesion layer between the polarizer and the adhesive layer in an unreacted state, or may be present therein after the functional groups have reacted. In addition, in the present invention, the easy-adhesion layer may be formed by applying an easy-adhesion composition to the entire surface of the adhesive layer-forming surface of the polarizer, or by applying an easy-adhesion composition to at least a portion of the surface.
[0047] X in the compound represented by the general formula (1) is a functional group containing a reactive group, which is a functional group capable of reacting with the curable component constituting the adhesive layer. Examples of the reactive group contained in X include a hydroxyl group, an amino group, an aldehyde group, a carboxyl group, a vinyl group, a (meth)acryloyl group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetanyl group, an α,β-unsaturated carbonyl group, a mercapto group, and a halogen group. In the case where the curable resin composition constituting the adhesive layer is active energy ray curable, the reactive group contained in X is preferably at least one reactive group selected from vinyl, (meth) acryloyl, styryl, (meth) acrylamide, vinyl ether, epoxy, oxetane and mercapto. In particular, in the case where the adhesive composition constituting the adhesive layer is free radical polymerizable, the reactive group contained in X is preferably at least one reactive group selected from (meth) acryloyl, styryl and (meth) acrylamide. In the case where the compound represented by the general formula (1) has a (meth) acrylamide, the reactivity is high and the copolymerization rate with the active energy ray curable resin composition is improved, which is more preferred. In addition, the (meth) acrylamide has high polarity and excellent adhesion, and therefore, it is also preferred from the perspective of efficiently obtaining the effect of the present invention. When the curable resin composition constituting the adhesive layer is cationically polymerizable, the reactive group contained in X preferably has at least one functional group selected from the group consisting of a hydroxyl group, an amino group, an aldehyde group, a carboxyl group, a vinyl ether group, an epoxy group, an oxetanyl group, and a mercapto group. In particular, when an epoxy group is included, the obtained curable resin layer has excellent adhesion to the adherend, which is preferred. When a vinyl ether group is included, the curable resin composition has excellent curability, which is preferred.
[0048] Preferred specific examples of the compound represented by the general formula (1) include compounds represented by the following general formula (1'):
[0049] [Chemical formula 6]
[0050]
[0051] (where Y is an organic group, X, R 1 and R 2 The same meaning as above.) Further preferred examples include the following compounds (1a) to (1d).
[0052] [Chemical formula 7]
[0053]
[0054] In the present invention, the compound represented by the general formula (1) may be a compound in which a reactive group is directly bonded to a boron atom, but as shown in the above specific examples, the compound represented by the general formula (1) is preferably a compound in which a reactive group is bonded to a boron atom via an organic group, that is, preferably a compound represented by the general formula (1'). In the case where the compound represented by the general formula (1) is a compound bonded to a reactive group, for example, via an oxygen atom bonded to a boron atom, there is a tendency for the adhesive water resistance of the polarizing film to deteriorate. On the other hand, when the compound represented by the general formula (1) does not have a boron-oxygen bond, but is bonded to an organic group via a boron atom, has a boron-carbon bond, and contains a reactive group (when it is the general formula (1')), the adhesive water resistance of the polarizing film is improved, and therefore it is preferred. The organic group specifically refers to an organic group having 1 to 20 carbon atoms which may have a substituent, and more specifically, for example, a linear or branched alkylene group having 1 to 20 carbon atoms which may have a substituent, a cyclic alkylene group having 3 to 20 carbon atoms which may have a substituent, a phenylene group having 6 to 20 carbon atoms which may have a substituent, and a naphthylene group having 10 to 20 carbon atoms which may have a substituent.
[0055] Examples of the compound represented by the general formula (1) include, in addition to the compounds exemplified above, esters of (meth)acrylic acid esters with boric acid, such as esters of hydroxyethylacrylamide with boric acid, esters of hydroxymethylacrylamide with boric acid, esters of hydroxyethyl acrylate with boric acid, and esters of hydroxybutyl acrylate with boric acid.
[0056] In the easy-adhesion composition, when the content of the compound represented by the general formula (1) is too small, the proportion of the compound represented by the general formula (1) present on the surface of the easy-adhesion layer may decrease, and the easy-adhesion effect may decrease. Therefore, in the easy-adhesion composition, the content of the compound represented by the general formula (1) is preferably 0.01% by weight or more, more preferably 0.05% by weight or more, and even more preferably 0.1% by weight or more.
[0057] In the present invention, the easy-adhesion composition contains the boron-containing compound described in the above formula (1), and one or both of an organic solvent having a boiling point of 85° C. or higher and a monomer having a polymerizable group having a boiling point of 85° C. or higher.
[0058] Examples of the organic solvent having a boiling point of 85° C. or higher include diacetone alcohol (boiling point 166° C.), ethylene glycol (boiling point 197.3° C.), acetic acid (boiling point 118° C.), 1-butanol (boiling point 117° C.), 2-butanol (boiling point 99.5° C.), cyclohexane (boiling point 161° C.), 1-hexanol (boiling point 156.5° C.), dipropylene glycol (boiling point 230.5° C.), propylene glycol (boiling point 187° C.), N,N-dimethylformamide (DMF) (boiling point 153° C.), glycerol diacetate (boiling point 280° C.), methyl cellosolve (boiling point 124.1° C.), tetramethylene sulfone (sulfolane) (boiling point 285° C.), glycerol 1,2-carbonate (boiling point 160° C. / 0.8 mmHg), N,N-dimethylacetamide (boiling point 165° C.), and dimethyl sulfoxide (DMSO) (boiling point 189° C.). From the viewpoint of coating properties, the boiling point of the organic solvent is preferably 90° C. or higher, more preferably 100° C. or higher. The upper limit of the boiling point of the organic solvent is not particularly limited, and may be, for example, about 300° C.
[0059] In the present invention, when the easy-adhesion composition used contains the above-mentioned organic solvent, from the viewpoint of improving the adhesion between the polarizer and the adhesive layer and improving the coating property, when the total amount of the easy-adhesion composition is set to 100 weight %, the content of the above-mentioned organic solvent is preferably 5 to 80 weight %, and more preferably 10 to 50 weight %. In addition, in the present invention, when the easy-adhesion composition used contains the above-mentioned organic solvent, from the viewpoint of improving the reactivity of the boron-containing compound to the functional group possessed by the polarizer and improving the adhesion between the polarizer and the adhesive layer, it is preferred to further contain water, and when the total amount of the easy-adhesion composition is set to 100 weight %, the content of water in this case is preferably 5 to 90 weight %, and more preferably 30 to 80 weight %.
[0060] As the polymerizable group possessed by the above-mentioned monomer having a boiling point of 85°C or more, for example, free radical polymerizable functional groups of carbon-carbon double bonds such as (meth)acryloyl and vinyl groups can be cited. As the above-mentioned monomer, for example, acryloyl morpholine (boiling point 158°C), ethylene glycol diacrylate (the number of n in the ethylene glycol part is ≈9) (boiling point 197.3°C), hydroxyethyl acrylamide (boiling point 124°C), N-vinyl pyrrolidone (boiling point 90°C), acrylic acid (boiling point 141°C), allyl alcohol (boiling point 97°C), etc. can be cited. From the viewpoint of coating properties, the boiling point of the above-mentioned monomer is above 90°C, and more preferably above 100°C. It should be noted that the upper limit of the boiling point of the above-mentioned monomer is not particularly limited, and for example, about 300°C can be exemplified.
[0061] In the present invention, when the easy-adhesion composition used contains the above-mentioned monomer, from the viewpoint of improving the adhesion between the polarizer and the adhesive layer and improving the coating property, when the total amount of the easy-adhesion composition is set to 100 weight %, the content of the above-mentioned monomer is preferably 5 to 80 weight %, and more preferably 10 to 50 weight %. In addition, in the present invention, when the easy-adhesion composition used contains the above-mentioned monomer, it is also preferable to further contain water from the viewpoint of improving the reactivity of the boron-containing compound to the functional group possessed by the polarizer and improving the adhesion between the polarizer and the adhesive layer. When the total amount of the easy-adhesion composition is set to 100 weight %, the content of water in this case is preferably 5 to 90 weight %, and more preferably 30 to 80 weight %.
[0062] In the present invention, the easy-adhesion composition may contain other additives, for example, a tackifier, an ultraviolet absorber, an antioxidant, a stabilizer such as a heat-resistant stabilizer, and the like.
[0063] <Adhesive layer>
[0064] In the method for manufacturing a polarizing film of the present invention, an easy-adhesive layer is formed by applying an easy-adhesive composition to the adhesive layer-forming surface of the polarizer and then providing a drying step as needed. In the present invention, when the thickness of the easy-adhesive layer of the polarizer is too thick, there is a case where the cohesive force of the easy-adhesive layer is reduced and the easy-adhesive effect is reduced. Therefore, when the polymerizable monomer volatilizes in the drying step and does not remain in the easy-adhesive layer, the thickness of the easy-adhesive layer is 300 nm or less, preferably 200 nm or less, and more preferably 100 nm or less from the viewpoint of productivity. On the other hand, as the lower limit of the thickness of the easy-adhesive layer for fully exerting the effect, the thickness of the monomolecular film of the compound represented by at least general formula (1) can be listed, which is usually 0.1 nm or more, preferably 1 nm or more, and more preferably 2 nm or more. When the polymerizable monomer does not volatilize in the drying step and remains in the easy-adhesive layer, the thickness of the easy-adhesive layer is 3 μm or less, preferably 2 μm or less, and more preferably 1 μm or less from the viewpoint of productivity. On the other hand, the minimum thickness for the adhesion layer to fully exert its effect is at least the thickness of the monomolecular film of the compound represented by the general formula (1), which is usually 0.1 nm or more, preferably 1 nm or more, and more preferably 2 nm or more.
[0065] When the content of the compound represented by the general formula (1) in the easy-adhesion layer is too small, the proportion of the compound represented by the general formula (1) present on the surface of the easy-adhesion layer decreases, and the easy-adhesion effect may be reduced. Therefore, the content of the compound represented by the general formula (1) in the easy-adhesion layer is preferably 0.01% by weight or more, more preferably 0.05% by weight or more, and further preferably 0.1% by weight or more.
[0066] <Adhesive layer>
[0067] The thickness of the adhesive layer is preferably 0.01 to 3.0 μm. When the thickness of the adhesive layer is too thin, the cohesive force of the adhesive layer is insufficient and the peeling force is reduced, which is not preferred. When the thickness of the adhesive layer is too thick, it is easy to cause peeling when stress is applied to the cross section of the polarizing film, and peeling failure caused by impact occurs, which is not preferred. The thickness of the adhesive layer is more preferably 0.1 to 2.5 μm, and most preferably 0.5 to 1.5 μm.
[0068] <Adhesive composition>
[0069] As the form of curing the adhesive composition, it can be roughly divided into thermal curing and active energy ray curing. As the resin constituting the thermosetting adhesive composition, polyvinyl alcohol resin, epoxy resin, unsaturated polyester, urethane resin, acrylic resin, urea resin, melamine resin, phenolic resin, etc. can be cited, and the curing agent is combined as needed. As the resin constituting the thermosetting adhesive composition, polyvinyl alcohol resin and epoxy resin are more preferably used. As an active energy ray curable adhesive composition, it can be roughly divided into electron beam curing, ultraviolet curing, and visible light curing based on the classification of active energy rays. In addition, as a cured form, it can be divided into free radical polymerizable adhesive compositions and cationic polymerizable adhesive compositions. In the present invention, active energy rays with a wavelength range of 10nm to less than 380nm are recorded as ultraviolet rays, and active energy rays with a wavelength range of 380nm to 800nm are recorded as visible light.
[0070] In the production of the polarizing film of the present invention, the adhesive composition is preferably active energy ray-curable, and particularly preferably visible light-curable by visible light of 380 nm to 450 nm.
[0071] As the curable component contained in the radical polymerizable adhesive composition, for example, the radical polymerizable compound used in the radical polymerizable adhesive composition can be cited. The radical polymerizable compound can be a compound having a radical polymerizable functional group of a carbon-carbon double bond such as a (meth)acryloyl group and a vinyl group. These curable components can use any one of a monofunctional radical polymerizable compound or a multifunctional radical polymerizable compound having more than two functions. In addition, these radical polymerizable compounds can be used alone or in combination of two or more. As these radical polymerizable compounds, for example, a compound having a (meth)acryloyl group is preferred. It should be noted that in the present invention, a (meth)acryloyl group refers to an acryloyl group and / or a methacryloyl group, and "(meth)" has the same meaning below.
[0072] Examples of the monofunctional radical polymerizable compound include compounds represented by the following general formula (2).
[0073] [Chemical formula 8]
[0074]
[0075] (Where R 3 is a hydrogen atom or a methyl group, R 4 and R 5 are each independently a hydrogen atom, an alkyl group, a hydroxyalkyl group, an alkoxyalkyl group or a cyclic ether group, R 4 and R 5 The number of carbon atoms in the alkyl group, hydroxyalkyl group, and / or alkoxyalkyl group is not particularly limited, and examples thereof include 1 to 4. 4 and R 5 The cyclic heterocycle which may be formed may be exemplified by N-acryloylmorpholine.
[0076] Specific examples of the compound represented by the general formula (2) include N-methyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-hexyl (meth)acrylamide and the like N-alkyl (meth)acrylamide derivatives; N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N-hydroxymethyl-N-propyl (meth)acrylamide and the like N-hydroxyalkyl (meth)acrylamide derivatives; N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide and the like N-alkoxy (meth)acrylamide derivatives. In addition, examples of the cyclic ether group-containing (meth)acrylamide derivatives include heterocyclic (meth)acrylamide derivatives in which the nitrogen atom of the (meth)acrylamide group forms a heterocyclic ring, such as N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylpyrrolidine and the like. Among these, N-hydroxyethyl acrylamide and N-acryloylmorpholine are preferably used from the viewpoints of excellent reactivity, obtaining a cured product having a high elastic modulus, and excellent adhesion to a polarizer.
[0077] From the viewpoint of improving the adhesion and water resistance when the polarizer and the transparent protective film are bonded via the adhesive layer, the content of the compound represented by the general formula (2) in the adhesive composition is preferably 0.01 to 80% by weight, more preferably 5 to 40% by weight.
[0078] The adhesive composition used in the present invention may contain other monofunctional radical polymerizable compounds as curable components in addition to the compound represented by general formula (1). Examples of the monofunctional radical polymerizable compounds include various (meth)acrylic acid derivatives having a (meth)acryloyloxy group. Specific examples include alkyl (meth)acrylates (having 1 to 20 carbon atoms) such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, tert-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, hexadecyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and n-octadecyl (meth)acrylate.
[0079] Examples of the (meth)acrylic acid derivatives include cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate and cyclopentyl (meth)acrylate; aralkyl (meth)acrylates such as benzyl (meth)acrylate; 2-isobornyl (meth)acrylate, 2-norbornyl methyl (meth)acrylate, 2-norbornyl methyl (meth)acrylate, 5-norbornene-2-yl methyl (meth)acrylate, 3-methyl-2-norbornyl methyl (meth)acrylate, Polycyclic (meth)acrylates such as dicyclopentenyl acrylate, dicyclopentenyloxyethyl (meth)acrylate, and dicyclopentanyl (meth)acrylate; (meth)acrylates containing alkoxy groups or phenoxy groups such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, and alkylphenoxypolyethylene glycol (meth)acrylate; etc. Among these, dicyclopentenyloxyethyl acrylate and phenoxyethyl acrylate are preferred because of their excellent adhesion to various protective films.
[0080] Examples of the (meth)acrylic acid derivatives include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate; hydroxyl-containing (meth)acrylates such as [4-(hydroxymethyl)cyclohexyl]methyl acrylate, cyclohexanedimethanol mono(meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate; epoxy-containing (meth)acrylates such as glycidyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate glycidyl ether; and 2,2,2-trifluoroethyl (meth)acrylate, 2,2 Halogen-containing (meth)acrylates such as 2-trifluoroethyl ethyl ester, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate; alkylaminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate; oxetanyl (meth)acrylate-containing (meth)acrylates such as 3-oxetanyl methyl (meth)acrylate, 3-methyloxetanyl methyl (meth)acrylate, 3-ethyloxetanyl methyl (meth)acrylate, 3-butyloxetanyl methyl (meth)acrylate, and 3-hexyloxetanyl methyl (meth)acrylate; (meth)acrylates having heterocyclic rings such as tetrahydrofurfuryl (meth)acrylate and butyrolactone (meth)acrylate, hydroxypivalic acid neopentyl glycol (meth)acrylate adduct, and p-phenylphenol (meth)acrylate. Among them, 2-hydroxy-3-phenoxypropyl acrylate is preferred because of its excellent adhesion to various protective films.
[0081] Examples of the monofunctional radical polymerizable compound include carboxyl group-containing monomers such as (meth)acrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0082] Examples of monofunctional free radical polymerizable compounds include lactam vinyl monomers such as N-vinylpyrrolidone, N-vinyl-ε-caprolactam, and methylvinylpyrrolidone; vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, and vinyl Vinyl monomers having a nitrogen-containing heterocyclic ring such as oxazole and vinyl morpholine, etc.
[0083] In the adhesive composition used in the present invention, when a hydroxyl-containing (meth)acrylate, a carboxyl-containing (meth)acrylate, a phosphoric acid-containing (meth)acrylate, etc. having high polarity in a monofunctional free radical polymerizable compound is contained, the adhesion to various substrates is improved. As the content of the hydroxyl-containing (meth)acrylate, it is preferably 1% to 30% by weight relative to the resin composition. When its content is too much, the water absorption rate of the cured product becomes high, and there is a situation where the water resistance deteriorates. As the content of the carboxyl-containing (meth)acrylate, it is preferably 1% to 20% by weight relative to the resin composition. When its content is too much, the optical durability of the polarizing film is reduced, so it is not preferred. As the phosphoric acid-containing (meth)acrylate, 2-(meth)acryloyloxyethyl acid phosphate can be cited. As its content, it is preferably 0.1% to 10% by weight relative to the resin composition. When its content is too much, the optical durability of the polarizing film is reduced, so it is not preferred.
[0084] In addition, as a monofunctional free radical polymerizable compound, a free radical polymerizable compound having an active methylene group can be used. The free radical polymerizable compound having an active methylene group is a compound having an active double bond group such as a (meth) acrylic group at the end or in the molecule and having an active methylene group. Examples of the active methylene group include acetoacetyl, alkoxymalonyl, or cyanoacetyl. The above-mentioned active methylene group is preferably acetoacetyl. Specific examples of the radical polymerizable compound having an active methylene group include acetoacetoxyethyl alkyl (meth)acrylates such as 2-acetoacetoxyethyl (meth)acrylate, 2-acetoacetoxyethyl propyl (meth)acrylate, and 2-acetoacetoxyethyl-1-methylethyl (meth)acrylate; 2-ethoxymalonyloxyethyl (meth)acrylate, 2-cyanoacetoxyethyl (meth)acrylate, N-(2-cyanoacetoxyethyl)acrylamide, N-(2-propionylacetoxybutyl)acrylamide, N-(4-acetoacetoxyethylmethylbenzyl)acrylamide, and N-(2-acetoacetylaminoethyl)acrylamide. The radical polymerizable compound having an active methylene group is preferably acetoacetoxyethyl alkyl (meth)acrylate.
[0085] Examples of the polyfunctional radical polymerizable compound having two or more functional groups include N,N'-methylenebis(meth)acrylamide as a polyfunctional (meth)acrylamide derivative, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol diacrylate, 2-ethyl-2-butylpropylene glycol di(meth)acrylate, bisphenol A di(meth)acrylate, bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A propylene oxide adduct di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, dimethacrylate, and the like. Esterification products of (meth)acrylic acid and polyols such as alkanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and EO-modified diglycerol tetra(meth)acrylate, and 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene. Specific examples thereof include ARONIX M-220 (manufactured by Toagosei Co., Ltd.), LIGHT ACRYLATE 1,9ND-A (manufactured by Kyoeisha Chemical Co., Ltd.), LIGHT ACRYLATE DGE-4A (manufactured by Kyoeisha Chemical Co., Ltd.), LIGHT ACRYLATE DCP-A (manufactured by Kyoeisha Chemical Co., Ltd.), SR-531 (manufactured by Sartomer Co., Ltd.), and CD-536 (manufactured by Sartomer Co., Ltd.). In addition, as required, various epoxy (meth)acrylates, urethane (meth)acrylates, polyester (meth)acrylates, various (meth)acrylate monomers, etc. It should be noted that the multifunctional (meth)acrylamide derivative is preferably included in the adhesive composition because it has not only a fast polymerization speed and excellent productivity, but also excellent crosslinking properties when the adhesive composition is made into a cured product.
[0086] From the viewpoint of combining adhesion with polarizers and various transparent protective films and optical durability under harsh environments, the free radical polymerizable compound preferably uses a monofunctional free radical polymerizable compound and a polyfunctional free radical polymerizable compound in combination. It should be noted that since the liquid viscosity of the monofunctional free radical polymerizable compound is low, the liquid viscosity of the resin composition can be reduced by containing the monofunctional free radical polymerizable compound in the resin composition. In addition, the monofunctional free radical polymerizable compound has a functional group that exhibits various functions in most cases. By containing the monofunctional free radical polymerizable compound in the resin composition, various functions can be exhibited in the resin composition and / or the cured product of the resin composition. The polyfunctional free radical polymerizable compound is preferably contained in the resin composition because it can make the cured product of the resin composition three-dimensionally cross-linked. For the ratio of the monofunctional free radical polymerizable compound to the polyfunctional free radical polymerizable compound, it is preferred to mix the polyfunctional free radical polymerizable compound in the range of 10 parts by weight to 1000 parts by weight relative to 100 parts by weight of the monofunctional free radical polymerizable compound.
[0087] When electron beams or the like are used as the active energy rays, the radical polymerizable adhesive composition does not need to contain a photopolymerization initiator. However, when ultraviolet rays or visible light are used as the active energy rays, the adhesive composition preferably contains a photopolymerization initiator.
[0088] The photopolymerization initiator in the case of using a free radical polymerizable compound can be appropriately selected according to the active energy ray. In the case of curing by ultraviolet light or visible light, a photopolymerization initiator that is cleaved by ultraviolet light or visible light is used. As the above-mentioned photopolymerization initiator, for example, benzophenone compounds such as benzil, benzophenone, benzoylbenzoic acid, 3,3′-dimethyl-4-methoxybenzophenone, 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α′-dimethylacetophenone, 2-methyl-2-hydroxypropiophenone, α-hydroxycyclohexylphenylketone and other aromatic ketone compounds; methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one and other acetophenone compounds; benzoin methyl ether , benzoin ether compounds such as benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, and anise methyl ether; aromatic ketal compounds such as benzil dimethyl ketal; aromatic sulfonyl chloride compounds such as 2-naphthalenesulfonyl chloride; photoactive oxime compounds such as 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)oxime; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropyl thioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropyl thioxanthone, and dodecylthioxanthone; camphorquinone; halogenated ketones; acylphosphine oxides; acylphosphonates, etc.
[0089] The amount of the photopolymerization initiator is 20% by weight or less relative to the total amount of the adhesive composition, preferably 0.01 to 20% by weight, more preferably 0.05 to 10% by weight, and even more preferably 0.1 to 5% by weight.
[0090] In addition, when the adhesive composition used in the present invention is used as a visible light curable adhesive containing a free radical polymerizable compound as a curable component, it is particularly preferred to use a photopolymerization initiator that is highly sensitive to light of 380 nm or more. The photopolymerization initiator that is highly sensitive to light of 380 nm or more will be described later.
[0091] As the photopolymerization initiator, it is preferred to use a compound represented by the following general formula (3) alone, or to use a compound represented by the general formula (3) in combination with a photopolymerization initiator having high sensitivity to light of 380 nm or longer described later.
[0092] [Chemical formula 9]
[0093]
[0094] (Where R 6 and R 7Represents -H, -CH2CH3, -iPr or Cl, R 6 and R 7 When the compound represented by the general formula (3) is used, the adhesion is excellent compared with the case where a photopolymerization initiator having high sensitivity to light of 380 nm or more is used alone. Among the compounds represented by the general formula (3), R 6 and R 7 The composition ratio of the compound represented by the general formula (3) in the curable resin composition is preferably 0.1 to 5 wt %, more preferably 0.5 to 4 wt %, and further preferably 0.9 to 3 wt % relative to the total amount of the curable resin composition.
[0095] In addition, it is preferred to add a polymerization initiation aid as needed. Examples of the polymerization initiation aid include triethylamine, diethylamine, N-methyldiethanolamine, ethanolamine, 4-dimethylaminobenzoic acid, methyl 4-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, isopentyl 4-dimethylaminobenzoate, and the like, with ethyl 4-dimethylaminobenzoate being particularly preferred. When a polymerization initiation aid is used, the amount thereof added is generally 0 to 5% by weight, preferably 0 to 4% by weight, and most preferably 0 to 3% by weight relative to the total amount of the curable resin composition.
[0096] In addition, as needed, known photopolymerization initiators can be used in combination. Since the transparent protective film with UV absorption ability does not transmit light below 380nm, it is preferred to use a photopolymerization initiator that is highly sensitive to light above 380nm as a photopolymerization initiator. Specifically, it can be listed as: 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(η5-2,4-cyclopentadiene-1-yl)bis(2,6-difluoro-3-(1H-pyrrole-1-yl)phenyl)titanium, etc.
[0097] In particular, as the photopolymerization initiator, in addition to the photopolymerization initiator of the general formula (3), it is preferred to further use a compound represented by the following general formula (4);
[0098] [Chemical formula 10]
[0099]
[0100] (Where R 8 , R 9 and R10 represents -H, -CH3, -CH2CH3, -iPr or Cl, R 8 , R 9 and R 10 The compounds represented by the general formula (4) may be the same or different. As the compound represented by the general formula (4), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one (trade name: IRGACURE907, manufacturer: BASF), which is a commercially available product, may be suitably used. In addition, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone (trade name: IRGACURE369, manufacturer: BASF) and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone (trade name: IRGACURE379, manufacturer: BASF) are preferred because of their high sensitivity.
[0101] In the above-mentioned adhesive composition, when a radical polymerizable compound having an active methylene group is used as the radical polymerizable compound, it is preferably used in combination with a radical polymerization initiator having a hydrogen abstraction effect. According to this composition, the adhesion of the adhesive layer possessed by the polarizing film is significantly improved, especially even just after being taken out of a high humidity environment or water (non-dry state). The reason is not yet clear, but it is believed to be the following. That is, the radical polymerizable compound having an active methylene group is polymerized together with other radical polymerizable compounds constituting the adhesive layer, and enters the main chain and / or side chain of the base polymer in the adhesive layer to form the adhesive layer. In this polymerization process, if there is a radical polymerization initiator having a hydrogen abstraction effect, the base polymer constituting the adhesive layer is formed, and hydrogen is abstracted from the radical polymerizable compound having an active methylene group to generate free radicals in the methylene group. Moreover, the methylene group generated by the free radical reacts with the hydroxyl group of the polarizer such as PVA to form a covalent bond between the adhesive layer and the polarizer. As a result, it is estimated that the adhesiveness of the adhesive layer included in the polarizing film is significantly improved even in a non-dried state.
[0102] In the present invention, as a free radical polymerization initiator having a hydrogen abstraction effect, for example, thioxanthone free radical polymerization initiators, benzophenone free radical polymerization initiators, etc. are listed. The above-mentioned free radical polymerization initiator is preferably a thioxanthone free radical polymerization initiator. As a thioxanthone free radical polymerization initiator, for example, a compound represented by the above-mentioned general formula (3) can be listed. As specific examples of the compound represented by the general formula (3), for example, thioxanthone, dimethylthioxanthone, diethylthioxanthone, isopropylthioxanthone, chlorothioxanthone, etc. can be listed. Among the compounds represented by the general formula (3), R is particularly preferred. 6 and R 7 It is diethylthioxanthone -CH2CH3.
[0103] When the above-mentioned adhesive composition contains a free radical polymerizable compound having an active methylene group and a free radical polymerization initiator having a hydrogen abstraction effect, when the total amount of the curable component is set to 100 weight %, it is preferred that the free radical polymerizable compound having an active methylene group is contained in an amount of 1 to 50 weight % and the free radical polymerization initiator is contained in an amount of 0.1 to 10 weight % relative to the total amount of the curable resin composition.
[0104] As described above, in the present invention, in the presence of a radical polymerization initiator having a hydrogen abstraction effect, the methylene group of the radical polymerizable compound having an active methylene group generates a free radical, and the methylene group reacts with the hydroxyl group of a polarizer such as PVA to form a covalent bond. Therefore, in order to generate a free radical from the methylene group of the radical polymerizable compound having an active methylene group and fully form the covalent bond, when the total amount of the curable component is set to 100% by weight, it is preferred to contain 1 to 50% by weight of the radical polymerizable compound having an active methylene group, and more preferably 3 to 30% by weight. In order to fully improve water resistance and improve adhesion in a non-dry state, it is preferred to set the radical polymerizable compound having an active methylene group to 1% by weight or more. On the other hand, if it exceeds 50% by weight, there is a case where the curing of the adhesive layer is poor. In addition, relative to the total amount of the adhesive composition, it is preferred to contain 0.1 to 10% by weight of a radical polymerization initiator having a hydrogen abstraction effect, and more preferably 0.3 to 9% by weight. In order to fully carry out the hydrogen abstraction reaction, it is preferred to use more than 0.1% by weight of a radical polymerization initiator. On the other hand, if the content is more than 10% by weight, the compound may not be completely dissolved in the composition.
[0105] The adhesive composition used in the present invention preferably further contains the following components as necessary.
[0106] In the present invention, the compound described in the above general formula (1), preferably the compound described in the above general formula (1'), and more preferably the compound described in the above general formulas (1a) to (1d) can be added to the adhesive composition. When these compounds are added to the adhesive composition, the adhesion to the polarizer and the transparent protective film is sometimes improved, which is preferred. From the viewpoint of improving the adhesion and water resistance between the polarizer and the cured layer, especially improving the adhesion and water resistance when the polarizer is bonded to the transparent protective film through the adhesive layer, the content of the compound described in the above general formula (1) in the adhesive composition is preferably 0.001 to 50% by weight, more preferably 0.1 to 30% by weight, and most preferably 1 to 10% by weight.
[0107] The bubble inhibitor is a compound that can reduce the surface tension by being added to the adhesive composition, thereby having the effect of reducing bubbles between the adhesive composition and the adherend to be bonded. As the bubble inhibitor, for example, a silicone bubble inhibitor having a polysiloxane skeleton such as polydimethylsiloxane, a (meth)acrylic bubble inhibitor having a (meth)acryloyl skeleton formed by polymerizing (meth)acrylate, a polyether bubble inhibitor formed by polymerizing vinyl ether, cyclic ether, etc., a fluorine bubble inhibitor formed by a fluorine-containing compound having a perfluoroalkyl group, etc., can be used, which has the effect of reducing the surface tension of the adhesive composition when added to the adhesive composition.
[0108] The bubble inhibitor preferably has a reactive group in the compound. In this case, when the polarizer and the transparent protective film are laminated, the generation of lamination bubbles can be reduced. As the reactive group possessed by the bubble inhibitor, polymerizable functional groups can be listed, specifically, free radical polymerizable functional groups with olefinic double bonds such as (meth) acryloyl, vinyl, allyl, epoxy groups such as glycidyl, oxetane, vinyl ether, cyclic ether, cyclic thioether, lactone, etc. can be listed. From the viewpoint of reactivity in the adhesive composition, it is preferred to have a bubble inhibitor with a double bond as a reactive group, and more preferably a bubble inhibitor with a (meth) acryloyl group.
[0109] In consideration of the lamination bubble suppression effect and the adhesion improvement effect, among the above bubble suppressors, silicone bubble suppressors are preferred. In addition, among the bubble suppressors, in consideration of the adhesion of the adhesive layer, bubble suppressors containing a urethane bond or an isocyanurate ring structure in the main chain skeleton or the side chain are preferred. As silicone bubble suppressors, commercially available products can also be suitably used, for example, "BYK-UV3505" (manufactured by BYK-Chemie Japan Co., Ltd.) which is an acryl-modified polydimethylsiloxane can be cited.
[0110] In order to achieve both the adhesive strength of the obtained adhesive layer and the effect of reducing lamination bubbles, the content of the bubble inhibitor is preferably 0.01 to 0.6% by weight when the total amount of the adhesive composition is 100% by weight.
[0111] In the adhesive composition used in the present invention, in addition to the curable component of the above-mentioned free radical polymerizable compound, an acrylic oligomer formed by polymerizing a (meth) acrylic acid monomer may also be contained. By containing the acrylic oligomer in the adhesive composition, the curing shrinkage when the composition is irradiated with active energy rays and cured can be reduced, and the interfacial stress between the adhesive and the adherends such as polarizers and transparent protective films can be reduced. As a result, the adhesion between the adhesive layer and the adherend can be suppressed. In order to fully suppress the curing shrinkage of the cured product layer (adhesive layer), the content of the acrylic oligomer is preferably less than 20% by weight, more preferably less than 15% by weight, relative to the total amount of the adhesive composition. When the content of the acrylic oligomer in the adhesive composition is too much, the reaction speed when the composition is irradiated with active energy rays is sharply reduced, and there is a situation where the curing becomes poor. On the other hand, relative to the total amount of the adhesive composition, it is preferred to contain more than 3% by weight of the acrylic oligomer, and more preferably more than 5% by weight.
[0112] In consideration of workability and uniformity during coating, the adhesive composition preferably has a low viscosity, and thus the acrylic oligomer obtained by polymerizing the (meth)acrylic acid monomer is also preferably a low viscosity. As a low-viscosity acrylic oligomer capable of preventing the curing shrinkage of the adhesive layer, its weight average molecular weight (Mw) is preferably 15,000 or less, more preferably 10,000 or less, and particularly preferably 5,000 or less. On the other hand, in order to fully suppress the curing shrinkage of the cured product layer (adhesive layer), the weight average molecular weight (Mw) of the acrylic oligomer is preferably 500 or more, more preferably 1,000 or more, and particularly preferably 1,500 or more.Specific examples of the (meth)acrylic monomer constituting the acrylic oligomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, tert-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, and tert-butyl (meth)acrylate. (meth)acrylate (carbon number 1-20) alkyl esters such as cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and n-octadecyl (meth)acrylate, and cycloalkyl (meth)acrylates (such as cyclohexyl (meth)acrylate and cyclopentyl (meth)acrylate), aralkyl (meth)acrylates (such as benzyl (meth)acrylate), polycyclic (meth)acrylates (such as 2-isobornyl (meth)acrylate, 2-isobornyl (meth)acrylate, and 2-isobornyl (meth)acrylate). methyl (meth)acrylate, 5-norbornene-2-ylmethyl (meth)acrylate, 3-methyl-2-norbornylmethyl (meth)acrylate, etc.), hydroxyl-containing (meth)acrylates (e.g. hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxypropylmethylbutyl (meth)acrylate, etc.), alkoxy- or phenoxy-containing (meth)acrylates (2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, (meth)acrylate ethyl carbitol ester, (meth)acrylate phenoxyethyl ester, etc.), epoxy-containing (meth)acrylates (such as (meth)acrylate glycidyl ester, etc.), halogen-containing (meth)acrylates (such as (meth)acrylate 2,2,2-trifluoroethyl ester, (meth)acrylate 2,2,2-trifluoroethyl ester, (meth)acrylate tetrafluoropropyl ester, (meth)acrylate hexafluoropropyl ester, (meth)acrylate octafluoropentyl ester, (meth)acrylate heptadecafluorodecyl ester, etc.), (meth)acrylate alkylaminoalkyl esters (such as (meth)acrylate dimethylaminoethyl ester, etc.). These (meth)acrylates can be used alone or in combination of two or more. Specific examples of acrylic oligomers include "ARUFON" manufactured by Toagosei Co., Ltd., "ACTFLOW" manufactured by Soken Chemical Co., Ltd., and "JONCRYL" manufactured by BASF Japan Ltd.
[0113] The adhesive composition may contain a photoacid generator. When the adhesive composition contains a photoacid generator, the water resistance and durability of the adhesive layer can be greatly improved compared to when the adhesive composition does not contain a photoacid generator. The photoacid generator can be represented by the following general formula (5).
[0114] General formula (5)
[0115] [Chemical formula 11]
[0116] L + X -
[0117] (Where L + Indicates any In addition, X - Indicates selected from PF66 - 、SbF6 - 、AsF6 - 、SbCl6 - 、BiCl5 - 、SnCl6 - 、ClO4 - , dithiocarbamate anion, SCN - The counter anion in . )
[0118] Next, the counter anion X in the general formula (5) - Provide explanation.
[0119] In principle, the counter anion X in the general formula (5) - There is no particular limitation, but non-nucleophilic anions are preferred. When the counter anion X is a non-nucleophilic anion, it is not easy to cause nucleophilic reactions of coexisting cations in the molecule or various materials used in combination, and as a result, the stability of the photoacid generator represented by the general formula (5) itself and the composition using the photoacid generator can be improved over time. The non-nucleophilic anion referred to here refers to an anion with a low ability to cause nucleophilic reactions. Examples of such anions include: PF6 - 、SbF6 - 、AsF6 - 、SbCl6 - 、BiCl5 - 、SnCl6 - 、ClO4 - , dithiocarbamate anion, SCN - wait.
[0120] Specifically, “CYRACURE UVI-6992”, “CYRACURE UVI-6974” (above, manufactured by Dow Chemical Japan Limited), “Adekaoptomer SP150”, “Adekaoptomer SP152”, “Adekaoptomer SP170”, “Adekaoptomer SP172” (above, manufactured by ADEKA Co., Ltd.), “IRGACURE 250” (manufactured by Ciba Specialty Chemicals Inc.), “CI-5102”, “CI-2855” (above, manufactured by Nippon Soda Co., Ltd.), “San-Aid SI-60L”, “San-Aid SI-80L”, “San-Aid SI-100L”, “San-Aid SI-110L”, “San-Aid SI-180L” (above, manufactured by Sanshin Chemical Co., Ltd.), “CPI-100P”, “CPI-100A” (above, manufactured by San-Apro Ltd.), "WPI-069", "WPI-113", "WPI-116", "WPI-041", "WPI-044", "WPI-054", "WPI-055", "WPAG-281", "WPAG-567", "WPAG-596" (all manufactured by Wako Pure Chemical Industries, Ltd.) can be cited as preferred specific examples of the photoacid generator of the present invention.
[0121] The content of the photoacid generator is 10 wt % or less, preferably 0.01 to 10 wt %, more preferably 0.05 to 5 wt %, particularly preferably 0.1 to 3 wt % based on the total amount of the adhesive composition.
[0122] The photobase generator is a compound that changes the molecular structure or cleaves the molecules by irradiation with ultraviolet light, visible light, etc., to generate one or more basic substances that can function as catalysts for the polymerization reaction of free radical polymerizable compounds and epoxy resins. Examples of basic substances include secondary amines and tertiary amines. Examples of photobase generators include the above-mentioned α-aminoacetophenone compounds, the above-mentioned oxime ester compounds, compounds having substituents such as acyloxyimino groups, N-formylated aromatic amino groups, N-acylated aromatic amino groups, nitrobenzyl carbamate groups, and alkoxybenzyl carbamate groups. Among them, oxime ester compounds are preferred.
[0123] Examples of the compound having an acyloxyimino group include O,O'-succinic acid dibenzoacetophenone oxime, O,O'-succinic acid dinaphthobenzophenone oxime, and a benzophenone oxime acrylate-styrene copolymer.
[0124] Examples of the compound having an N-formylated aromatic amino group or an N-acylated aromatic amino group include di-N-(p-formylamino)diphenylmethane, di-N-(p-acetylamino)diphenylmethane, di-N-(p-benzamido)diphenylmethane, 4-formylaminostilbene, 4-acetylaminostilbene, 2,4-diformylaminostilbene, 1-formylaminonaphthalene, 1-acetylaminonaphthalene, 1,5-diformylaminonaphthalene, 1-formylaminoanthracene, 1,4-diformylaminoanthracene, 1-acetylaminoanthracene, 1,4-diformylaminoanthraquinone, 1,5-diformylaminoanthraquinone, 3,3′-dimethyl-4,4′-diformylaminobiphenyl, and 4,4′-diformylaminobenzophenone.
[0125] Examples of the compound having a nitrobenzyl carbamate group and an alkoxybenzyl carbamate group include bis{{(2-nitrobenzyl)oxy}carbonyl}diaminodiphenylmethane, 2,4-bis{(2-nitrobenzyl)oxy}stilbene, bis{(2-nitrobenzyloxy)carbonyl}hexane-1,6-diamine, and o-xylidine{{(2-nitro-4-chlorobenzyl)oxy}amide.
[0126] The photobase generator is preferably at least one selected from an oxime ester compound and an α-aminoacetophenone compound, and is more preferably an oxime ester compound. As the α-aminoacetophenone compound, an α-aminoacetophenone compound having two or more nitrogen atoms is particularly preferred.
[0127] As other photobase generators, WPBG-018 (trade name, 9-anthrylmethyl N,N'-diethylcarbamate), WPBG-027 (trade name, (E)-1-[3-(2-hydroxyphenyl)-2-propenoyl]piperidine), WPBG-082 (trade name, guanidinium2-(3-benzoylphenyl)propionate), WPBG-140 (trade name, 1-(anthraquinon-2-yl)ethylimidazolecarboxylate) and the like can be used.
[0128] In the above adhesive composition, a photoacid generator and a compound containing either an alkoxy group or an epoxy group may be used in combination in the adhesive composition.
[0129] When using a compound having one or more epoxy groups in the molecule or a polymer (epoxy resin) having two or more epoxy groups in the molecule, a compound having two or more functional groups reactive with epoxy groups in the molecule can be used in combination. Among them, the functional group reactive with epoxy groups can be listed, for example, as carboxyl, phenolic hydroxyl, mercapto, primary or secondary aromatic amino, etc. Considering the three-dimensional curing property, it is particularly preferred to have two or more of these functional groups in one molecule.
[0130] Examples of polymers having one or more epoxy groups in the molecule include epoxy resins, including bisphenol A type epoxy resins derived from bisphenol A and epichlorohydrin, bisphenol F type epoxy resins derived from bisphenol F and epichlorohydrin, bisphenol S type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, bisphenol F novolac type epoxy resins, alicyclic epoxy resins, diphenyl ether type epoxy resins, hydroquinone type epoxy resins, naphthalene type epoxy resins, biphenyl type epoxy resins, fluorene type epoxy resins, trifunctional epoxy resins, tetrafunctional epoxy resins and other multifunctional epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, hydantoin type epoxy resins, isocyanurate type epoxy resins, aliphatic chain epoxy resins, and the like. These epoxy resins may be halogenated or hydrogenated. Examples of commercially available epoxy resin products include JER code 828, 1001, 801N, 806, 807, 152, 604, 630, 871, YX8000, YX8034, and YX4000 manufactured by Japan Epoxy Resin, EPICLON830, EXA835LV, HP4032D, and HP820 manufactured by DIC Corporation, EP4100 series, EP4000 series, and EPU series manufactured by ADEKA Corporation, and Daicel Chemical Co., Ltd. Industries, Ltd. CELLOXIDE series (2021, 2021P, 2083, 2085, 3000, etc.), Epolead series, EHPE series, YD series, YDF series, YDCN series, YDB series, phenoxy resin (polyhydroxy polyether synthesized from bisphenols and epichlorohydrin, and having epoxy groups at both ends; YP series, etc.), Denacol series made by Nagase ChemteX Corporation, Epolight series made by Kyoeisha Chemical Co., Ltd., etc., but not limited to these. These epoxy resins can be used in combination of two or more.
[0131] The compound having an alkoxy group in the molecule is not particularly limited as long as it has one or more alkoxy groups in the molecule, and a known compound can be used. Representative examples of such compounds include melamine compounds, amino resins, and silane coupling agents.
[0132] The amount of the compound containing any one of an alkoxy group and an epoxy group is usually 30% by weight or less relative to the total amount of the adhesive composition. If the content of the compound in the composition is too much, the adhesion is reduced, and the impact resistance to the drop hammer test is sometimes deteriorated. The content of the compound in the composition is more preferably 20% by weight or less. On the other hand, from the perspective of water resistance, it is preferred that the compound be contained in the composition at 2% by weight or more, and more preferably at 5% by weight or more.
[0133] When the adhesive composition used in the present invention is active energy ray-curable, it is preferable to use an active energy ray-curable compound as the silane coupling agent. However, even if it is not active energy ray-curable, similar water resistance can be imparted.
[0134] Specific examples of the silane coupling agent include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, p-phenylvinyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane, which are active energy ray-curable compounds.
[0135] 3-Methacryloxypropyltrimethoxysilane and 3-acryloxypropyltrimethoxysilane are preferred.
[0136] As a specific example of the inactive energy ray-curable silane coupling agent, a silane coupling agent having an amino group is preferred. As a specific example of the silane coupling agent having an amino group, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-aminopropyl triisopropoxysilane, γ-aminopropyl methyl dimethoxysilane, γ-aminopropyl methyl diethoxysilane, γ-(2-aminoethyl)aminopropyl trimethoxysilane, γ-(2-aminoethyl)aminopropyl methyl dimethoxysilane, γ-(2-aminoethyl)aminopropyl triethoxysilane, γ-(2-aminoethyl)aminopropyl methyl diethoxysilane, γ-(2-aminoethyl)aminopropyl triisopropoxysilane, γ-(2-(2-aminoethyl)aminoethyl)aminopropyl trimethoxysilane, γ-(6-aminohexyl)aminopropyl trimethoxysilane , 3-(N-ethylamino)-2-methylpropyltrimethoxysilane, γ-ureidopropyltrimethoxysilane, γ-ureidopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, N-benzyl-γ-aminopropyltrimethoxysilane, N-vinylbenzyl-γ-aminopropyltriethoxysilane, N-cyclohexylaminomethyltriethoxysilane, N-cyclohexylaminomethyldiethoxymethylsilane, N-phenylaminomethyltrimethoxysilane, (2-aminoethyl)aminomethyltrimethoxysilane, N,N'-bis[3-(trimethoxysilyl)propyl]ethylenediamine and other amino-containing silanes; N-(1,3-dimethylbutylene)-3-(triethoxysilyl)-1-propylamine and other ketimine-type silanes.
[0137] The silane coupling agent having an amino group may be used alone or in combination. Among these, in order to ensure good adhesion, γ-aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropylmethyldiethoxysilane, and N-(1,3-dimethylbutylene)-3-(triethoxysilyl)-1-propylamine are preferred.
[0138] The amount of the silane coupling agent is preferably in the range of 0.01 to 20% by weight, more preferably 0.05 to 15% by weight, and even more preferably 0.1 to 10% by weight relative to the total amount of the adhesive composition. This is because when the amount is greater than 20% by weight, the storage stability of the adhesive composition deteriorates, and when it is less than 0.1% by weight, it is difficult to fully exert the effect of water resistance of the adhesive.
[0139] Specific examples of the inactive energy ray-curable silane coupling agents other than those mentioned above include 3-ureidopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, and imidazole silane.
[0140] When the adhesive composition used in the present invention contains a compound having a vinyl ether group, the water resistance of the bonding between the polarizer and the adhesive layer is improved, so it is preferred. The reason for this effect is not clear, but one of the reasons is speculated that the bonding force between the polarizer and the adhesive layer is improved through the interaction between the vinyl ether group of the compound and the polarizer. In order to further improve the water resistance of the bonding between the polarizer and the adhesive layer, the compound is preferably a free radical polymerizable compound having a vinyl ether group. In addition, with respect to the content of the compound, it is preferably 0.1 to 19 weight % relative to the total amount of the adhesive composition.
[0141] The adhesive composition used in the present invention may contain a compound that produces keto-enol tautomerism. For example, in an adhesive composition containing a crosslinking agent or an adhesive composition that can be used in combination with a crosslinking agent, it is preferred to use a method that contains the above-mentioned compound that produces keto-enol tautomerism. Thus, the excessive viscosity increase, gelation, and microgel formation of the adhesive composition after the organic metal compound is combined can be suppressed, and the effect of extending the pot life of the composition can be achieved.
[0142] As the above-mentioned compound that produces keto-enol tautomerism, various β-dicarbonyl compounds can be used. As specific examples, β-diketones such as acetylacetone, 2,4-hexanedione, 3,5-heptanedione, 2-methylhexane-3,5-dione, 6-methylheptane-2,4-dione, and 2,6-dimethylheptane-3,5-dione can be listed; acetoacetic acid esters such as methyl acetoacetate, ethyl acetoacetate, isopropyl acetoacetate, and tert-butyl acetoacetate; propionoacetic acid esters such as methyl propionoacetate, ethyl propionoacetate, isopropyl propionoacetate, and tert-butyl propionoacetate; isobutyrylacetates such as methyl isobutyrylacetate, ethyl isobutyrylacetate, isopropyl isobutyrylacetate, and tert-butyl isobutyrylacetate; malonic acid esters such as methyl malonate and ethyl malonate; etc. Among them, acetylacetone and acetoacetic acid esters can be listed as suitable compounds. The above-mentioned compounds that undergo keto-enol tautomerism may be used alone or in combination of two or more.
[0143] The amount of the compound that produces keto-enol tautomerism can be set to 0.05 to 10 parts by weight, preferably 0.2 to 3 parts by weight (e.g., 0.3 to 2 parts by weight) relative to 1 part by weight of the organometallic compound. If the amount of the above compound is less than 0.05 parts by weight relative to 1 part by weight of the organometallic compound, it is sometimes difficult to exert a sufficient effect. On the other hand, if the amount of the compound is greater than 10 parts by weight relative to 1 part by weight of the organometallic compound, it is sometimes difficult to exhibit the target water resistance due to excessive interaction with the organometallic compound.
[0144] The adhesive composition of the present invention may also contain a polyrotaxane. The polyrotaxane has a cyclic molecule, a linear molecule penetrating the opening of the cyclic molecule, and a capping group disposed at both ends of the linear molecule so that the cyclic molecule does not detach from the linear molecule. Preferably, the cyclic molecule has an active energy ray-curable functional group.
[0145] The cyclic molecule is not particularly limited as long as its opening includes a linear molecule in a string, can move on the linear molecule, and has an active energy ray polymerizable group. It should be noted that in this specification, the "cyclic" of "cyclic molecule" means substantially "cyclic". That is, as long as it can move on the linear molecule, the cyclic molecule may not be completely ring-closed.
[0146] As specific examples of cyclic molecules, cyclic polymers such as cyclic polyethers, cyclic polyesters, cyclic polyetheramines, and cyclodextrins such as α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin can be listed. Among them, α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, and other cyclodextrins that are relatively easy to obtain and can select a variety of chain-capping groups are preferred. Two or more cyclic molecules can be mixed in a polyrotaxane or an adhesive.
[0147] In the polyrotaxane used in the present invention, the cyclic molecule has an active energy ray polymerizable group. Thus, the polyrotaxane reacts with the active energy ray curable component to obtain an adhesive whose crosslinking points are movable even after curing. The active energy ray polymerizable group possessed by the cyclic molecule can be any group that can polymerize with the active energy ray curable compound, and examples thereof include free radical polymerizable groups such as (meth)acryloyl and (meth)acryloyloxy groups.
[0148] When cyclodextrin is used as the cyclic molecule, it is preferred to introduce an active energy ray polymerizable group into the hydroxyl group of cyclodextrin via any appropriate linker. The number of active energy ray polymerizable groups in one molecule of polyrotaxane is preferably 2 to 1280, more preferably 50 to 1000, and even more preferably 90 to 900.
[0149] It is preferred to introduce a hydrophobic modifying group into the cyclic molecule. By introducing a hydrophobic modifying group, the compatibility with the active energy ray-curable component can be improved. In addition, since the hydrophobicity is imparted, when used in a polarizing film, water can be prevented from penetrating into the interface between the adhesive layer and the polarizer, and the water resistance can be further improved. Examples of the hydrophobic modifying group include polyester chains, polyamide chains, alkyl chains, oxyalkylene chains, ether chains, and the like. As specific examples, the groups described in
[0027] to
[0042] of WO2009 / 145073 can be cited.
[0150] The polarizing film using a resin composition containing a polyrotaxane as an adhesive has excellent water resistance. The reason for the improved water resistance of the polarizing film has not yet been determined, but it is speculated as follows. That is, it is believed that due to the mobility of the cyclic molecules of the polyrotaxane, the cross-linking points can move (the so-called pulley effect), thereby imparting flexibility to the cured adhesive and increasing the adhesion to the surface unevenness of the polarizer, thereby preventing water from invading the interface between the polarizer and the adhesive layer. In addition, it is believed that by giving the polyrotaxane a hydrophobic modifying group, the adhesive can be imparted with hydrophobicity, which also helps to prevent water from invading the interface between the polarizer and the adhesive layer. The content of the polyrotaxane is preferably 2% by weight to 50% by weight relative to the resin composition.
[0151] In the present invention, a cationically polymerizable adhesive composition can be used to form an adhesive layer. Cationic polymerizable compounds used in the cationically polymerizable adhesive composition can be classified into monofunctional cationically polymerizable compounds having one cationically polymerizable functional group in the molecule and polyfunctional cationically polymerizable compounds having two or more cationically polymerizable functional groups in the molecule. Since the liquid viscosity of the monofunctional cationically polymerizable compound is relatively low, the liquid viscosity of the resin composition can be reduced by including the monofunctional cationically polymerizable compound in the resin composition. In addition, the monofunctional cationically polymerizable compound often has a functional group that exhibits various functions. By including the monofunctional cationically polymerizable compound in the resin composition, various functions can be exhibited in the resin composition and / or the cured product of the resin composition. The polyfunctional cationically polymerizable compound is preferably included in the resin composition because it can make the cured product of the resin composition three-dimensionally cross-linked. For the ratio of the monofunctional cationic polymerizable compound to the polyfunctional cationic polymerizable compound, it is preferred to mix the polyfunctional cationic polymerizable compound in a range of 10 to 1000 parts by weight relative to 100 parts by weight of the monofunctional cationic polymerizable compound. As cationic polymerizable functional groups, epoxy groups, oxetane groups, and vinyl ether groups can be listed. As compounds having epoxy groups, aliphatic epoxy compounds, alicyclic epoxy compounds, and aromatic epoxy compounds can be listed. Due to their excellent curability and adhesion, it is particularly preferred to contain alicyclic epoxy compounds as the cationic polymerizable adhesive composition of the present invention. Examples of the alicyclic epoxy compound include 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, caprolactone-modified products of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, trimethyl caprolactone-modified products, and valerolactone-modified products. Specifically, examples include CELLOXIDE 2021, CELLOXIDE 2021A, CELLOXIDE 2021P, CELLOXIDE 2081, CELLOXIDE 2083, and CELLOXIDE 2085 (all manufactured by Daicel Chemical Industries, Ltd.), Cyracure UVR-6105, Cyracure UVR-6107, Cyracure 30, and R-6110 (all manufactured by Dow Chemical Japan Ltd.). It is preferred that the compound contain an oxetane group because it has the effect of improving the curability of the cationically polymerizable adhesive composition of the present invention and reducing the liquid viscosity of the composition.Examples of the compound having an oxetane group include 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyl-3-oxetane)methoxymethyl]benzene, 3-ethyl-3-(phenoxymethyl)oxetane, di[(3-ethyl-3-oxetane)methyl]ether, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, and novolac oxetane. Commercially available compounds include ARONOXETANE OXT-101, ARON OXETANE OXT-121, ARON OXETANE OXT-211, ARON OXETANE OXT-221, and ARON OXETANE OXT-212 (all manufactured by Toagosei Co., Ltd.). It is preferred that the compound having a vinyl ether group be contained because it has the effect of improving the curability of the cationically polymerizable adhesive composition of the present invention and reducing the liquid viscosity of the composition. Examples of the compound having a vinyl ether group include 2-hydroxyethyl vinyl ether, diethylene glycol monovinyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, triethylene glycol divinyl ether, cyclohexanedimethanol divinyl ether, cyclohexanedimethanol monovinyl ether, tricyclodecane vinyl ether, cyclohexyl vinyl ether, methoxyethyl vinyl ether, ethoxyethyl vinyl ether, and pentaerythritol tetravinyl ether.
[0152] The cationic polymerizable adhesive composition contains at least one compound selected from the above-described compounds having an epoxy group, a compound having an oxetane group, and a compound having a vinyl ether group as a curable component, and they are all substances that are cured by cationic polymerization, so a photocationic polymerization initiator is added. The photocationic polymerization initiator generates cationic species or Lewis acids by irradiation with active energy rays such as visible light, ultraviolet rays, X-rays, and electron beams, thereby initiating polymerization reactions of epoxy groups and oxetane groups. As the photocationic polymerization initiator, a photoacid generator and a photobase generator can be used appropriately, and the photoacid generator described later can be used appropriately. In addition, when the adhesive composition used in the present invention is used as a visible light curable, it is particularly preferred to use a photocationic polymerization initiator with high sensitivity to light above 380nm, but the photocationic polymerization initiator is a compound that usually shows maximum absorption near 300nm or in a wavelength region shorter than 300nm, therefore, by cooperating with a photosensitizer that shows maximum absorption under a wavelength region longer than it, specifically, a light with a wavelength longer than 380nm, it is possible to sense light of a wavelength near it, and promote the generation of cationic species or acids from the photocationic polymerization initiator. As photosensitizers, for example, anthracene compounds, pyrene compounds, carbonyl compounds, organic sulfur compounds, persulfides, redox compounds, azo and diazo compounds, halogen compounds, photoreduction pigments, etc., can be cited, and they can also be mixed with more than two kinds for use. In particular, the photosensitizing effect of anthracene compounds is excellent, so it is preferred, and specifically Anthracure UVS-1331 and Anthracure UVS-1221 (Kawasaki Chemical Co., Ltd.) can be cited. The content of the photosensitizer is preferably 0.1% by weight to 5% by weight, more preferably 0.5% by weight to 3% by weight.
[0153] <Polarizing filter>
[0154] In the present invention, from the viewpoint of improving optical durability in a harsh environment under high temperature and high humidity, a thin polarizer having a thickness of 3 μm or more and 15 μm or less is preferably used as the polarizer. In particular, it is preferably 12 μm or less, more preferably 10 μm or less, and particularly preferably 8 μm or less. Such a thin polarizer has less uneven thickness, excellent visual recognition, and less dimensional change, and therefore has excellent durability against thermal shock.
[0155] It should be noted that thin polarizers generally have a low moisture content, specifically, in most cases the moisture content is 15% by weight or less. Such a thin polarizer with a low moisture content has the above-mentioned effects, but on the other hand, the reactivity with the boron-containing compound contained in the easy-adhesion composition used in the present invention is low, and sometimes the effect of improving the adhesion between the polarizer and the adhesive layer is insufficient. Therefore, in the method for manufacturing a polarizing film of the present invention, when a polarizer with a moisture content of 15% by weight or less is used, it is preferred that the easy-adhesion composition contains water. Specifically, when the total amount of the composition is set to 100% by weight, the water content is preferably 5 to 90% by weight, and more preferably 30 to 80% by weight.
[0156] The polarizer uses a polyvinyl alcohol resin. Examples of the polarizer include films obtained by adsorbing dichroic substances such as iodine and dichroic dyes on hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified films of ethylene-vinyl acetate copolymers and then uniaxially stretching them, and polyene oriented films such as dehydrated products of polyvinyl alcohol and dehydrochlorinated products of polyvinyl chloride. Among these, a polarizer formed of a polyvinyl alcohol film and a dichroic substance such as iodine is preferred.
[0157] A polarizer formed by dyeing a polyvinyl alcohol film with iodine and uniaxially stretching can be made, for example, as follows: dyeing is performed by immersing polyvinyl alcohol in an aqueous solution of iodine, and stretching to 3 to 7 times the initial length. As required, it can also be immersed in an aqueous solution of boric acid, zinc sulfate, zinc chloride, or potassium iodide. In addition, as required, the polyvinyl alcohol film can also be immersed in water and washed before dyeing. By washing the polyvinyl alcohol film with water, not only can the stains and anti-blocking agents on the surface of the polyvinyl alcohol film be cleaned, but it also has the effect of preventing uneven dyeing, etc. by swelling the polyvinyl alcohol film. Stretching can be performed after dyeing with iodine, or it can be stretched while dyeing, and it can also be dyed with iodine after stretching. It can also be stretched in an aqueous solution of boric acid, potassium iodide, etc., or in a water bath.
[0158] From the perspective of tensile stability and humidification reliability, the polarizer preferably contains boric acid. In addition, from the perspective of suppressing the occurrence of through cracks, the content of boric acid contained in the polarizer is preferably 22% by weight or less, and more preferably 20% by weight or less relative to the total amount of the polarizer. From the perspective of tensile stability and humidification reliability, the content of boric acid is preferably 10% by weight or more, and more preferably 12% by weight or more relative to the total amount of the polarizer.
[0159] Representative thin polarizers include those described in Japanese Patent No. 4751486, Japanese Patent No. 4751481, Japanese Patent No. 4815544, Japanese Patent No. 5048120, International Publication No. 2014 / 077599, International Publication No. 2014 / 077636, etc., or those obtained by the production methods described in these documents.
[0160] As the above-mentioned thin polarizer, in the manufacturing method including the step of stretching in the state of a laminate and the step of dyeing, from the viewpoint of being able to stretch to a high ratio and improving the polarization performance, it is preferable to use a thin polarizer obtained by a manufacturing method including the step of stretching in a boric acid aqueous solution as described in Japanese Patent No. 4751486, Japanese Patent No. 4751481, and Japanese Patent No. 4815544, and it is particularly preferable to use a thin polarizer obtained by a manufacturing method including the step of auxiliary stretching in a gas atmosphere before stretching in a boric acid aqueous solution as described in Japanese Patent No. 4751481 and Japanese Patent No. 4815544. These thin polarizing films can be obtained by a manufacturing method including the step of stretching a polyvinyl alcohol resin (hereinafter, also referred to as a PVA resin) layer and a stretching resin substrate in the state of a laminate and the step of dyeing. According to this production method, even if the PVA-based resin layer is thin, it can be stretched by being supported by the stretchable resin substrate without causing problems such as breakage due to stretching.
[0161] <Transparent protective film>
[0162] As a transparent protective film, it is preferred that the transparency, mechanical strength, thermal stability, moisture barrier, isotropy, etc. are excellent. For example, polyester polymers such as polyethylene terephthalate and polyethylene naphthalate, cellulose polymers such as cellulose diacetate and cellulose triacetate, acrylic polymers such as polymethyl methacrylate, polystyrene, polyolefin polymers such as acrylonitrile-styrene copolymer (AS resin), polycarbonate polymers, etc. can be listed. In addition, polyethylene, polypropylene, polyolefins with ring or norbornene structures, polyolefin polymers such as ethylene-propylene copolymers, vinyl chloride polymers, nylon, amide polymers such as aromatic polyamides, imide polymers, sulfone polymers, polyethersulfone polymers, polyetheretherketone polymers, polyphenylene sulfide polymers, vinyl alcohol polymers, vinylidene chloride polymers, vinyl butyral polymers, polyarylate polymers, polyoxymethylene polymers, epoxy polymers, or mixtures of the above polymers can also be listed as examples of polymers forming the above transparent protective film. The transparent protective film may contain one or more arbitrary appropriate additives. Examples of additives include ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, colorants, and the like. The content of the thermoplastic resin in the transparent protective film is preferably 50 to 100% by weight, more preferably 50 to 99% by weight, further preferably 60 to 98% by weight, and particularly preferably 70 to 97% by weight. When the content of the thermoplastic resin in the transparent protective film is less than 50% by weight, there is a concern that the high transparency originally possessed by the thermoplastic resin cannot be fully exhibited.
[0163] In addition, as a transparent protective film, a polymer film described in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can be cited, such as (A) a resin composition containing a thermoplastic resin having a substituted and / or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted and / or unsubstituted phenyl and nitrile group in the side chain. As a specific example, a film of a resin composition containing an alternating copolymer formed by isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be cited. The film can be formed by a mixed extrusion product of the resin composition. These films have a small phase difference and a small photoelastic coefficient, so they can eliminate the unevenness caused by the strain of the polarizing film. In addition, the moisture permeability is small, so the humidification durability is excellent.
[0164] In addition, in the present invention, the moisture permeability of the transparent protective film preferably used is 150 g / m 2 / 24h or less. According to this structure, moisture in the air is not easy to enter the polarizing film, and the change of the moisture content of the polarizing film itself can be suppressed. As a result, the curling and dimensional change of the polarizing film caused by the storage environment can be suppressed.
[0165] As the transparent protective film provided on one or both sides of the polarizer, a transparent protective film having excellent transparency, mechanical strength, thermal stability, moisture barrier property, isotropy, etc. is preferred, and a moisture permeability of 150 g / m 2 / 24h or less, particularly preferably 120g / m 2 / 24h or less, more preferably 5 to 70 g / m2 / 24h.
[0166] As the material for forming the transparent protective film satisfying the above-mentioned low moisture permeability, polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polycarbonate resins; polyarylate resins; amide resins such as nylon and aromatic polyamide; polyolefin polymers such as polyethylene, polypropylene, and ethylene-propylene copolymers, cyclic olefin resins having a cyclic or norbornene structure, (meth) acrylic resins, or mixtures thereof can be used. Among the above-mentioned resins, polycarbonate resins, cyclic polyolefin resins, and (meth) acrylic resins are preferred, and cyclic polyolefin resins and (meth) acrylic resins are particularly preferred.
[0167] The thickness of the transparent protective film can be appropriately determined, and is generally preferably 5 to 100 μm, particularly preferably 10 to 60 μm, and more preferably 13 to 40 μm from the viewpoints of strength, workability such as handling properties, and thinness.
[0168] The above-mentioned transparent protective film usually uses a transparent protective film with a front phase difference of less than 40nm and a thickness direction phase difference of less than 80nm. The front phase difference Re is represented by Re=(nx-ny)×d. The thickness direction phase difference Rth is represented by Rth=(nx-nz)×d. In addition, the Nz coefficient is represented by Nz=(nx-nz) / (nx-ny). [Wherein, the refractive indices in the slow axis direction, fast axis direction and thickness direction of the film are set to nx, ny, nz respectively, and d (nm) is set to the thickness of the film. The slow axis direction is set to the direction in which the refractive index in the film surface reaches the maximum. ]. It should be noted that the transparent protective film is preferably as colorless as possible. It is preferred to use a protective film with a phase difference value in the thickness direction of -90nm to +75nm. By using a protective film with a phase difference value (Rth) in the thickness direction of -90nm to +75nm, the coloring (optical coloring) of the polarizing film caused by the transparent protective film can be basically eliminated. The thickness direction retardation value (Rth) is more preferably -80 nm to +60 nm, particularly preferably -70 nm to +45 nm.
[0169] On the other hand, as the above-mentioned transparent protective film, a phase difference plate having a front phase difference of 40 nm or more and / or a thickness direction phase difference of 80 nm or more can be used. The front phase difference is usually controlled to a range of 40 to 200 nm, and the thickness direction phase difference is usually controlled to a range of 80 to 300 nm. When a phase difference plate is used as a transparent protective film, the phase difference plate also acts as a transparent protective film, so that thinning can be achieved.
[0170] As a phase difference plate, there can be listed: a birefringent film formed by unidirectional or bidirectional stretching of a polymer raw material, an oriented film of a liquid crystal polymer, a phase difference plate formed by an oriented layer of a liquid crystal polymer supported by a film, etc. The thickness of the phase difference plate is not particularly limited, and is usually about 20 to 150 μm. As a polymer raw material, for example: polyvinyl alcohol, polyvinyl butyral, polymethyl vinyl ether, polyhydroxyethyl acrylate, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, polycarbonate, polyacrylate, polysulfone, polyethylene terephthalate, polyethylene naphthalate, polyether sulfone, polyphenylene sulfide, polyphenylene ether, polyallyl sulfonic acid, polyamide, polyimide, polyolefin, polyvinyl chloride, cellulose resin, cyclic polyolefin resin (norbornene resin), or various copolymers, graft copolymers, mixtures thereof, etc. These polymer raw materials become oriented objects (stretched films) by stretching, etc.
[0171] As liquid crystal polymers, for example, various liquid crystal polymers of main chain type and side chain type, etc., which introduce conjugated linear atomic groups (mesogens) that impart liquid crystal orientation into the main chain of the polymer and the side chain, can be listed. As a specific example of a main chain type liquid crystal polymer, a structure in which a mesogen group is bonded by a spacer that imparts bending, such as a polyester liquid crystal polymer of nematic orientation, a discotic polymer, a cholesteric polymer, etc. can be listed. As a specific example of a side chain type liquid crystal polymer, a liquid crystal polymer having a mesogen part composed of a para-substituted cyclic compound unit imparting nematic orientation as a side chain with polysiloxane, polyacrylate, polymethacrylate or polymalonate as the main chain skeleton, and a spacer composed of conjugated atomic groups can be listed. These liquid crystal polymers are, for example, liquid crystal polymers formed by grinding the surface of a film such as polyimide and polyvinyl alcohol formed on a glass plate, liquid crystal polymers formed by oblique evaporation of silicon oxide, etc., and a solution of a liquid crystal polymer is developed on its orientation treatment surface and heat-treated.
[0172] The phase difference plate can be, for example, various wave plates, a phase difference plate with an appropriate phase difference depending on the purpose of use, such as the purpose of utilizing the coloring of the birefringence of the liquid crystal layer, the purpose of compensating for the viewing angle, etc., or it can be a phase difference plate in which two or more phase difference plates are stacked to control optical properties such as phase difference.
[0173] The phase difference plate can be selected to use a phase difference plate that satisfies the relationship of nx=ny>nz, nx>ny>nz, nx>ny=nz, nx>nz>ny, nz=nx>ny, nz>nx>ny, nz>nx=ny according to various uses. It should be noted that ny=nz includes not only the case where ny and nz are completely the same, but also the case where ny and nz are substantially the same.
[0174] For example, among the phase difference plates satisfying nx>ny>nz, it is preferred to use a phase difference plate whose front phase difference satisfies 40 to 100nm, whose thickness direction phase difference satisfies 100 to 320nm, and whose Nz coefficient satisfies 1.8 to 4.5. For example, for the phase difference plate (positive A plate) satisfying nx>ny=nz, it is preferred to use a phase difference plate whose front phase difference satisfies 100 to 200nm. For example, for the phase difference plate (negative A plate) satisfying nz=nx>ny, it is preferred to use a phase difference plate whose front phase difference satisfies 100 to 200nm. For example, for the phase difference plate satisfying nx>nz>ny, it is preferred to use a phase difference plate whose front phase difference satisfies 150 to 300nm, and whose Nz coefficient satisfies greater than 0 and less than 0.7. In addition, as described above, for example, a phase difference plate satisfying nx=ny>nz, nz>nx>ny, or nz>nx=ny can be used.
[0175] The transparent protective film can be appropriately selected according to the liquid crystal display device to be applied. For example, in the case of VA (Vertical Alignment, including MVA, PVA), it is preferred that the transparent protective film on at least one side (unit side) of the polarizing film has a phase difference. As a specific phase difference, it is preferably in the range of Re=0~240nm, Rth=0~500nm. When recorded in three-dimensional refractive index, it is preferred that nx>ny=nz, nx>ny>nz, nx>nz>ny, nx=ny>nz (positive A plate, biaxial, negative C plate) is used. In the VA type, it is preferably used in the form of a combination of a positive A plate and a negative C plate, or a bidirectional film. When a polarizing film is used on the upper and lower sides of the liquid crystal unit, the upper and lower sides of the liquid crystal unit may both have a phase difference, or any of the upper and lower transparent protective films may have a phase difference.
[0176] For example, it can be used in the case of IPS (In-Plane Switching, including FFS), the case where the transparent protective film on one side of the polarizing film has a phase difference, or the case where there is no phase difference. For example, the case where there is no phase difference is preferably the case where the upper and lower sides (unit sides) of the liquid crystal unit also have no phase difference. The case where there is a phase difference is preferably the case where both the upper and lower sides of the liquid crystal unit have a phase difference, or the case where either the upper and lower sides have a phase difference (for example, the upper side has a bidirectional film satisfying the relationship nx>nz>ny, and the lower side has no phase difference, or the upper side has a positive A plate, and the lower side has a positive C plate). In the case where there is a phase difference, the range of Re=-500~500nm and Rth=-500~500nm is preferred. When recorded in three-dimensional refractive index, nx>ny=nz, nx>nz>ny, nz>nx=ny, nz>nx>ny (positive A plate, biaxial, positive C plate) are preferred.
[0177] The transparent protective film may be further laminated with a releasable substrate to improve its mechanical strength and handling properties. The releasable substrate may be peeled off from the laminate containing the transparent protective film and the polarizer before or after laminating the transparent protective film and the polarizer, during the process or in another process.
[0178] Hereinafter, each step in the method for producing a polarizing film of the present invention will be described.
[0179] The method for producing a polarizing film of the present invention is a method for producing a polarizing film in which a transparent protective film is provided on at least one surface of a polarizer via an adhesive layer, and the method comprises a coating step of coating an easily adhesive composition on the adhesive layer-formed surface of the polarizer.
[0180] It should be noted that the polarizer and the transparent protective film can be subjected to surface modification treatment before the coating process. It is particularly preferred to perform surface modification treatment on the surface of the polarizer. Examples of surface modification treatments include corona treatment, plasma treatment, excimer treatment, and flame treatment, with corona treatment being particularly preferred. By performing corona treatment, reactive functional groups such as carbonyl and amino groups are generated on the surface of the polarizer, and the adhesion with the adhesive layer is improved. In addition, impurities on the surface can be removed or surface unevenness can be reduced by an ashing effect, thereby making a polarizing film with excellent appearance characteristics.
[0181] <Step of applying the easy-adhesion composition>
[0182] In the present invention, the easy-adhesive composition can be applied on one side of the polarizer, or on both sides of the polarizer. As a method for applying the easy-adhesive composition on the adhesive layer forming surface side of the polarizer, it can be appropriately selected according to the viscosity and target thickness of the composition. From the perspective of removing foreign matter on the surface of the polarizer and coating properties, it is preferred to use a post-measurement coating method. As a specific example of the post-measurement coating method, a gravure roller coating method, a forward roller coating method, an air knife coating method, a rod / rod coating method, etc. can be cited. Among these, from the perspective of removing foreign matter on the surface of the polarizer and coating properties, a gravure roller coating method is particularly preferred.
[0183] In the gravure roller coating method, various patterns can be formed on the surface of the gravure roller, for example, a honeycomb pattern, a trapezoidal pattern, a lattice pattern, a conical pattern or a diagonal line pattern can be formed. In order to effectively prevent the appearance defects of the polarizing film finally obtained, the pattern formed on the surface of the gravure roller is preferably a honeycomb pattern. In the case of the honeycomb pattern, in order to improve the surface accuracy of the coating surface after applying the easy-adhesive composition, the unit volume is preferably 1 to 5 cm 3 / m 2 , more preferably 2 to 3 cm 3 / m 2 Similarly, in order to improve the surface accuracy of the coating surface after coating the easy-adhesion composition, the number of unit lines per inch of the roller is preferably 200 to 3000 lines / inch. In addition, the rotation speed ratio of the gravure roller relative to the travel speed of the polarizer is preferably 100 to 300%.
[0184] <Drying step of the easy-adhesion composition>
[0185] In the method for manufacturing a polarizing film of the present invention, a polarizer with an easy-adhesive layer can be formed by coating an easy-adhesive composition on the adhesive layer-forming surface of the polarizer, or by providing a drying step as needed after the coating step of the easy-adhesive composition. The drying step can use a step known to those skilled in the art, such as an air-drying step, a heating step, or a hot air-drying step.
[0186] The manufacturing method of the polarizing film of the present invention includes: a coating step of an easy-bonding composition; a coating step of an adhesive composition, after forming a polarizer with an easy-bonding layer through a drying step of the easy-bonding composition as needed, and then coating the adhesive composition on the easy-bonding layer forming surface of the polarizer with the easy-bonding layer and at least one side of a transparent protective film; a bonding step of bonding the polarizer and the transparent protective film; and a bonding step of irradiating active energy rays from the polarizer surface side or the transparent protective film surface side to bond the polarizer and the transparent protective film through the adhesive layer obtained by curing the adhesive composition.
[0187] <Adhesive composition application step>
[0188] The method for applying the adhesive composition can be appropriately selected according to the viscosity and target thickness of the composition, and examples thereof include a reverse coater, a gravure coater (direct, reverse, or offset), a rod-type reverse coater, a roll coater, a die coater, a wire rod coater, a rod coater, and the like.
[0189] <Lamination process>
[0190] The polarizer and the transparent protective film are bonded together using the adhesive composition applied as described above. The bonding of the polarizer and the transparent protective film can be performed using a roll laminator or the like.
[0191] <Bonding process>
[0192] After the polarizer and the transparent protective film are attached, active energy rays (electron beam, ultraviolet rays, visible light, etc.) are irradiated to cure the adhesive composition, thereby forming an adhesive layer. The irradiation direction of the active energy rays (electron beam, ultraviolet rays, visible light, etc.) can be irradiated from any appropriate direction. It is preferably irradiated from the transparent protective film side. If irradiated from the polarizer side, there is a concern that the polarizer will deteriorate due to the active energy rays (electron beam, ultraviolet rays, visible light, etc.).
[0193] The irradiation conditions in the case of electron beam irradiation can be any appropriate conditions as long as they are conditions that can cure the above-mentioned adhesive composition. For example, the acceleration voltage of electron beam irradiation is preferably 5kV to 300kV, and more preferably 10kV to 250kV. When the acceleration voltage is less than 5kV, there is a concern that the electron beam cannot reach the adhesive and the curing becomes insufficient. If the acceleration voltage is greater than 300kV, there is a concern that the penetration force through the sample is too strong and the transparent protective film and polarizer are damaged. As for the irradiation dose, it is 5 to 100kGy, and more preferably 10 to 75kGy. When the irradiation dose is less than 5kGy, the adhesive is not sufficiently cured. If it is greater than 100kGy, the transparent protective film and polarizer are damaged, the mechanical strength is reduced, yellowing occurs, and the given optical properties cannot be obtained.
[0194] Electron beam irradiation is usually performed in an inert gas, but can be performed in the atmosphere with a small amount of oxygen introduced as needed. Depending on the material of the transparent protective film, oxygen is appropriately introduced so that the surface of the transparent protective film that is first contacted by the electron beam is contacted, oxygen barrier occurs, and damage to the transparent protective film can be prevented, so that only the adhesive can be efficiently irradiated with the electron beam.
[0195] In the method for manufacturing the polarizing film of the present invention, as the active energy ray, it is preferred to use an active energy ray containing visible light in the wavelength range of 380nm to 450nm, especially an active energy ray with the largest irradiation amount of visible light in the wavelength range of 380nm to 450nm. When ultraviolet rays, visible light, and a transparent protective film endowed with ultraviolet absorption ability (ultraviolet non-transmissive transparent protective film) are used, light with a wavelength shorter than about 380nm is absorbed, so light with a wavelength shorter than 380nm does not reach the adhesive composition and does not contribute to its polymerization reaction. In addition, the light with a wavelength shorter than 380nm absorbed by the transparent protective film is converted into heat, and the transparent protective film itself generates heat, which becomes the cause of defects such as curling / wrinkling of the polarizing film. Therefore, in the present invention, when ultraviolet rays and visible light are used, it is preferred to use a device that does not emit light with a wavelength shorter than 380 nm as an active energy ray generating device. More specifically, the ratio of the cumulative illuminance in the wavelength range of 380 to 440 nm to the cumulative illuminance in the wavelength range of 250 to 370 nm is preferably 100:0 to 100:50, and more preferably 100:0 to 100:40. In the method for manufacturing a polarizing film of the present invention, as active energy rays, a metal halide lamp enclosed in gallium or an LED light source that emits light in the wavelength range of 380 to 440 nm is preferred. Alternatively, a light source containing ultraviolet rays and visible light, such as a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, an incandescent lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a metal halide lamp, a fluorescent lamp, a tungsten lamp, a gallium lamp, an excimer laser or sunlight, can be used, and ultraviolet rays with a wavelength shorter than 380 nm can also be blocked by a bandpass filter before use. In order to improve the adhesion performance of the adhesive layer between the polarizer and the transparent protective film and prevent curling of the polarizing film, it is preferred to use a metal halide lamp encapsulated with gallium, and use active energy rays obtained by a bandpass filter that can block light with a wavelength shorter than 380nm, or active energy rays with a wavelength of 405nm obtained using an LED light source.
[0196] It is preferred to heat the adhesive composition before irradiation with ultraviolet rays or visible light (pre-irradiation heating), in which case, it is preferably heated to 40° C. or higher, more preferably heated to 50° C. or higher. It is also preferred to heat the active energy ray-curable adhesive composition after irradiation with ultraviolet rays or visible light (post-irradiation heating), in which case, it is preferably heated to 40° C. or higher, more preferably heated to 50° C. or higher.
[0197] The adhesive composition used in the present invention can be particularly suitably used in the case of forming an adhesive layer formed by bonding a polarizer to a transparent protective film having a transmittance of less than 5% at a wavelength of 365 nm. Here, the adhesive composition used in the present invention contains the photopolymerization initiator of the above-mentioned general formula (3), and can be cured to form an adhesive layer by irradiating ultraviolet rays through a transparent protective film having UV absorption ability. Therefore, even for a polarizing film having a transparent protective film having UV absorption ability laminated on both sides of a polarizer, the adhesive layer can be cured. However, of course, for a polarizing film having a transparent protective film without UV absorption ability laminated, the adhesive layer can also be cured. It should be noted that the transparent protective film having UV absorption ability refers to a transparent protective film having a transmittance of less than 10% for light at 380 nm.
[0198] Examples of a method for imparting UV absorption capability to a transparent protective film include a method of incorporating an ultraviolet absorber into the transparent protective film and a method of laminating a surface treatment layer containing an ultraviolet absorber on the surface of the transparent protective film.
[0199] Specific examples of the ultraviolet absorber include conventionally known oxybenzophenone compounds, benzotriazole compounds, salicylate compounds, benzophenone compounds, cyanoacrylate compounds, nickel complex compounds, triazine compounds, and the like.
[0200] When the polarizing film of the present invention is manufactured by a continuous production line, the line speed varies depending on the curing time of the adhesive composition, and is preferably 1 to 500 m / min, more preferably 5 to 300 m / min, and further preferably 10 to 100 m / min. If the line speed is too low, productivity is insufficient, or damage to the transparent protective film is too large, and a polarizing film that can withstand durability tests, etc. cannot be produced. If the line speed is too high, sometimes the curing of the curable resin composition becomes insufficient, and the target adhesion cannot be obtained.
[0201] <Optical film>
[0202] The polarizing film of the present invention can be used as an optical film laminated with other optical layers in practical use. The optical layer is not particularly limited, and examples thereof include optical layers that are sometimes used in the formation of liquid crystal display devices, such as phase difference films (including wave plates such as 1 / 2 wave plates and 1 / 4 wave plates), visual compensation films, brightness enhancement films, reflective plates, and anti-transmission plates.
[0203] As the retardation film, a retardation film having a front retardation of 40 nm or more and / or a thickness direction retardation of 80 nm or more can be used. The front retardation is usually controlled to be in the range of 40 to 200 nm, and the thickness direction retardation is usually controlled to be in the range of 80 to 300 nm.
[0204] As the phase difference plate, there are: birefringent films obtained by uniaxial or biaxial stretching of polymer raw materials, oriented films of liquid crystal polymers, and phase difference plates obtained by supporting the oriented layer of liquid crystal polymers with films. The thickness of the phase difference film is not particularly limited, and is generally about 20 to 150 μm.
[0205] As the retardation film, a reverse wavelength dispersion type retardation film satisfying the following formulas (1) to (3) can be used:
[0206] 0.70<Re
[450] / Re
[550] <0.97···(1)
[0207] 1.5×10 -3 <Δn<6×10 -3 ···(2)
[0208] 1.13<NZ<1.50···(3)
[0209] (Wherein, Re
[450] and Re
[550] are the in-plane phase difference values of the phase difference film measured at 23°C using light of wavelengths of 450nm and 550nm, respectively; Δn is nx-ny, i.e., in-plane birefringence, when the refractive indices in the slow axis direction and fast axis direction of the phase difference film are set to nx and ny, respectively; NZ is the ratio of nx-nz to nx-ny when nz is set to the refractive index in the thickness direction of the phase difference film, wherein nx-nz is the birefringence in the thickness direction and nx-ny is the in-plane birefringence).
[0210] The polarizing film or the optical film laminated with at least one polarizing film may be provided with an adhesive layer for bonding with other components such as a liquid crystal cell. The adhesive forming the adhesive layer is not particularly limited, and an adhesive having a base polymer such as acrylic polymer, silicone polymer, polyester, polyurethane, polyamide, polyether, fluorine, rubber, etc. may be appropriately selected and used. It is particularly preferred to use an adhesive such as an acrylic adhesive that has excellent optical transparency and exhibits appropriate adhesive properties such as wettability, cohesion and adhesion, and has excellent weather resistance, heat resistance, etc.
[0211] The adhesive layer may be provided on one or both sides of the polarizing film or optical film in the form of a laminated layer of layers of different compositions or types. In addition, when provided on both sides, adhesive layers of different compositions, types, thicknesses, etc. may be formed on the surface and back of the polarizing film or optical film. The thickness of the adhesive layer may be appropriately determined according to the purpose of use, adhesive strength, etc., and is usually 1 to 500 μm, preferably 1 to 200 μm, and particularly preferably 1 to 100 μm.
[0212] The exposed surface of the adhesive layer is temporarily covered by a diaphragm for the purpose of preventing contamination during the period until it is actually used. Thus, it is possible to prevent contact with the adhesive layer under normal handling conditions. As a diaphragm, in addition to the above-mentioned thickness conditions, a diaphragm such as a diaphragm coated with a suitable thin layer such as a plastic film, a rubber sheet, paper, a cloth, a non-woven fabric, a net, a foam sheet, a metal foil, or a laminate thereof with a suitable release agent such as silicone, a long-chain alkyl, a fluorine, or molybdenum sulfide as required can be used.
[0213] <Image Display Device>
[0214] The polarizing film or optical film of the present invention can be preferably used for forming various devices such as liquid crystal display devices. The formation of the liquid crystal display device can be carried out in a conventional manner. That is, the liquid crystal display device is usually formed by appropriately assembling a liquid crystal cell with a polarizing film or optical film, and components such as a lighting system used as needed, and loading a driving circuit, etc. In the present invention, except for the use of the polarizing film or optical film of the present invention, there is no particular limitation, and it can be carried out in a conventional manner. Regarding the liquid crystal cell, any type of liquid crystal cell such as TN type, STN type, π type, etc. can be used.
[0215] Suitable liquid crystal display devices such as a liquid crystal display device with a polarizing film or an optical film disposed on one side or both sides of a liquid crystal cell, and a liquid crystal display device using a backlight or a reflector in the lighting system can be formed. In this case, the polarizing film or the optical film of the present invention can be disposed on one side or both sides of the liquid crystal cell. In the case where the polarizing film or the optical film is disposed on both sides, they can be the same or different. Furthermore, when forming the liquid crystal display device, one or more layers of suitable components such as a diffusion plate, an anti-glare layer, an anti-reflection film, a protective plate, a prism array, a lens array sheet, a light diffusion plate, a backlight, etc. can be disposed at a suitable position.
[0216] Example
[0217] Although examples of the present invention are described below, the embodiments of the present invention are not limited to these.
[0218] <Polarizing filter>
[0219] First, a laminate having a 9 μm thick PVA layer formed on an amorphous PET substrate is subjected to auxiliary stretching in a gas atmosphere at a stretching temperature of 130° C. to form a stretched laminate. Next, the stretched laminate is dyed to form a colored laminate. The colored laminate is further stretched in a boric acid aqueous solution at a stretching temperature of 65 degrees to form an optical film laminate including a 5 μm thick PVA layer in an integrated manner. By such two-step stretching, an optical film laminate including a 5 μm thick PVA layer constituting a thin polarizer can be obtained. The PVA molecules of the PVA layer formed on the amorphous PET substrate undergo a high-order orientation, and the iodine adsorbed by dyeing undergoes a high-order orientation in one direction in the form of a polyiodide ion complex. The water content of the thin polarizer (PVA layer) is 10% by weight.
[0220] <Transparent protective film A>
[0221] By a twin-shaft mixer, 100 parts by weight of the imidized MS resin described in the manufacturing example 1 of Japanese Patent Publication No. 2010-284840 and 0.62 parts by weight of a triazine ultraviolet absorber (manufactured by ADEKA Co., Ltd., trade name: T-712) were mixed at 220°C to prepare resin particles. The obtained resin particles were dried at 100.5 kPa and 100°C for 12 hours, extruded from a T die head at a die temperature of 270°C by a single screw extruder, and formed into a film (thickness 160 μm). The film was further stretched in an atmosphere at 150°C along its conveying direction (thickness 80 μm), and then after applying an easy-adhesive agent containing an aqueous urethane resin, it was stretched in an atmosphere at 150°C in a direction orthogonal to the film conveying direction to obtain a transparent protective film A with a thickness of 40 μm.
[0222] <Transparent protective film B>
[0223] As the transparent protective film B, a 60 μm-thick cellulose triacetate film (manufactured by Fuji Film Co., Ltd.: FUJITAC TG60UL) was used.
[0224] <Active energy rays>
[0225] As active energy rays, visible light (gallium-enclosed metal halide lamp) was used. Irradiation device: Light HAMMER 10 manufactured by Fusion UV Systems, Inc., valve: V valve, peak illuminance: 1600 mW / cm 2 , cumulative irradiation 1000 / mJ / cm 2 (Wavelength: 380 to 440 nm) The illuminance of visible light was measured using the Sola-Check system manufactured by Solatell.
[0226] (Preparation of Easy Adhesion Composition)
[0227] The easy-adhesion compositions used in Examples 1 to 9 and Comparative Examples 1 to 3 were prepared according to the compositions described in Table 1. Details of the raw materials described in Table 1 are shown below.
[0228] (1) Boron-containing compounds
[0229] 3-Acrylamidephenylboronic acid; manufactured by Junsei Chemical Co., Ltd.
[0230] (2) Leveling agent
[0231] Product name: "OLFINE EXP.4200", manufactured by Nissin Chemical Industry Co., Ltd.
[0232] (3) A monomer having a polymerizable group with a boiling point of 85°C or higher
[0233] Acryloylmorpholine (boiling point 158°C); trade name "ACMO", manufactured by Kojin Co., Ltd.
[0234] Ethylene glycol diacrylate (the number of n in the ethylene glycol portion is ≈ 9) (boiling point 197.3°C); trade name "LIGHTACRYLATE 9EG-A", manufactured by Kyoeisha Chemical Co., Ltd.
[0235] Hydroxyethyl acrylamide (boiling point 124°C); trade name "HEAA", manufactured by Kojin Co., Ltd.
[0236] (4) Organic solvents with a boiling point of 85°C or above
[0237] Diacetone alcohol (boiling point 166°C)
[0238] Ethylene glycol (boiling point 197.3°C)
[0239] (5) Diluent
[0240] Water (boiling point 100℃)
[0241] Isopropyl alcohol (boiling point 82.4°C)
[0242] (Step of applying the easy-adhesion composition)
[0243] The easy-adhesive composition described in Table 1 was applied to the PVA surface of the optical film laminate including a PVA layer having a thickness of 5 μm of the polarizer using a gravure roll coating method with a gravure roll, and hot air dried at 25° C. for 1 minute to produce a polarizer with an easy-adhesive layer. In the coating process of each embodiment and comparative example, the thickness before drying (wet thickness) and the thickness after drying (dry thickness) when the easy-adhesive composition was applied are shown in Table 1.
[0244] (Applicability Evaluation)
[0245] In the coating process of each example and comparative example, the case where no lateral unevenness occurred during coating was evaluated as ○, and the case where lateral unevenness occurred was evaluated as ×. In addition, the case where the gravure roll and the polarizer did not stick was evaluated as ○, and the case where sticking occurred was evaluated as ×. The results are shown in Table 1.
[0246] (Preparation of Adhesive Composition)
[0247] When the total amount of the composition is 100% by weight, 43.0% by weight of acryloylmorpholine, 43.0% by weight of 1,9-nonanediol diacrylate (trade name "LIGHT ACRYLATE 1.9ND-A", manufactured by Kyoeisha Chemical Co., Ltd.), 9.7% by weight of an acrylic oligomer obtained by polymerizing a (meth)acrylic monomer (trade name "ARUFON UG4010", manufactured by Toagosei Co., Ltd.), 2.9% by weight of diethylthioxanthone (a compound represented by the general formula (3), trade name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.) as a photoinitiator, and 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one (a compound represented by the general formula (4), trade name "IRGACURE The mixture was mixed with 1.4 wt % of 907" (manufactured by BASF Corporation) and stirred at 50° C. for 1 hour to prepare adhesive compositions used in Examples and Comparative Examples.
[0248] (Production of polarizing film)
[0249] Using an MCD coater (manufactured by Fuji Machine Co., Ltd.) (unit shape: honeycomb, gravure roller line number: 1000 lines / inch, rotation speed 140% / pair of line speed), the above-mentioned adhesive composition was applied to the bonding surface side of the transparent protective film A to a thickness of 0.7 μm, thereby forming an uncured adhesive layer. Next, a transparent protective film was bonded from the easy bonding layer side of the above-mentioned polarizer with an easy bonding layer using a roller machine. Then, the above-mentioned visible light was irradiated from the bonded transparent protective film side using an active energy ray irradiation device to bond the polarizer to the transparent protective film, and then hot air dried at 70°C for 3 minutes to peel off and remove the amorphous PET substrate laminated on the other side of the polarizer, thereby obtaining a polarizing film having a transparent protective film on one side of the polarizer. Bonding was performed at a line speed of 25 m / min. In order to evaluate the water-resistant adhesion, a polarizing film was manufactured using the transparent protective film B in the same manner as described above.
[0250] (Evaluation of water-resistant adhesion (initial adhesion))
[0251] The obtained polarizing film was cut into 200 mm in a direction parallel to the stretching direction of the polarizer and 15 mm in a direction orthogonal to the polarizer, and the polarizing film was bonded to a glass plate. Then, a cutter was used to cut an incision between the transparent protective film and the polarizer, and the protective film and the polarizer were peeled off at a peeling speed of 300 m / min in a tensile testing machine in a 90-degree direction, and the peeling strength (N / 15 mm) was measured. In addition, the infrared absorption spectrum of the peeled surface after peeling was measured by the ATR method, and the peeling morphology was evaluated according to the following criteria. The results are shown in Table 1.
[0252] ○: The transparent protective film material is damaged or the polarizer material is damaged
[0253] ×: The interface between the transparent protective film and the adhesive layer is peeled off, or the interface between the polarizer and the adhesive layer is peeled off.
[0254] (Evaluation of water-resistant adhesion (cold water immersion peeling test))
[0255] The polarizing film obtained in each example was cut into a size of 200 mm in a direction parallel to the stretching direction of the polarizer and 20 mm in a perpendicular direction. The polarizing film was immersed in pure water at 23°C for 24 hours and then taken out. After wiping with a dry cloth, an incision was made between the protective film and the polarizer with a cutter, and the polarizing film was bonded to the glass plate. The transparent protective film and the polarizer were peeled off in a 90-degree direction at a peeling speed of 10 m / min using a tensile testing machine, and the peeling strength was measured. It should be noted that the above evaluation was performed within 1 minute after the polarizing film was taken out of the pure water. The results are shown in Table 1.
[0256] (Evaluation of water-resistant adhesion (harsh cold water immersion peeling test))
[0257] The polarizing film obtained in each example was cut into a size of 200 mm in a direction parallel to the stretching direction of the polarizer and 20 mm in a perpendicular direction. The polarizing film was immersed in pure water at 23°C for 48 hours and then taken out. After wiping with a dry cloth, an incision was made between the protective film and the polarizer with a cutter, and the polarizing film was bonded to the glass plate. The transparent protective film and the polarizer were peeled off in a 90-degree direction at a peeling speed of 10 m / min using a tensile testing machine, and the peeling strength was measured. It should be noted that the above evaluation was performed within 1 minute after the polarizing film was taken out of the pure water. The results are shown in Table 1.
[0258]
Claims
1. A method for producing a polarizing film, wherein a transparent protective film is provided on at least one side of a polarizer via an adhesive layer, The method comprises a coating step of coating an easy-adhesion composition on the adhesive layer-forming surface of the polarizer, in, The easy-adhesive composition comprises: water, A compound represented by the following general formula (1), and One or both of an organic solvent having a boiling point of 85° C. or higher and a monomer having a polymerizable group having a boiling point of 85° C. or higher, Furthermore, when the total amount of the easy-adhesion composition is set to 100 wt %, the content of water is 5 to 68.9 wt %. In the formula, X is a functional group containing a reactive group, R 1 and R 2 Each independently represents a hydrogen atom, an aliphatic hydrocarbon group which may have a substituent, an aryl group or a heterocyclic group.
2. The method for producing a polarizing film according to claim 1, wherein: The compound represented by the general formula (1) is replaced by a compound represented by the following general formula (1'): In the formula, Y is an organic group, X, R 1 and R 2 Same meaning as above.
3. The method for producing a polarizing film according to claim 1 or 2, wherein: The reactive group possessed by the compound represented by the general formula (1) is at least one reactive group selected from the group consisting of a (meth)acrylamide group, an α,β-unsaturated carbonyl group, a vinyl group, a vinyl ether group, an epoxy group, an oxetanyl group, an amino group, an aldehyde group, a mercapto group and a halogen group.
4. The method for producing a polarizing film according to claim 1 or 2, wherein: The water content of the polarizer is 15% by weight or less.
5. The method for producing a polarizing film according to claim 1 or 2, wherein: The coating step is a step of coating the easy-adhesion composition using a post-measurement coating method.
6. The method for manufacturing a polarizing film according to claim 5, wherein: The post-measurement coating method is a gravure roll coating method using a gravure roll.
7. A polarizer with an easy-adhesion layer, wherein the easy-adhesion layer is formed on at least one side of the polarizer. in, The easy-adhesion layer contains: water, A compound represented by the following general formula (1), and One or both of an organic solvent having a boiling point of 85° C. or higher and a monomer having a polymerizable group having a boiling point of 85° C. or higher, Furthermore, when the total amount of the easy-adhesive composition forming the easy-adhesive layer is 100 wt %, the content of water is 5 to 68.9 wt %. In the formula, X is a functional group containing a reactive group, R 1 and R 2 Each independently represents a hydrogen atom, an aliphatic hydrocarbon group which may have a substituent, an aryl group or a heterocyclic group.
8. The polarizer with an easy-adhesion layer according to claim 7, wherein The compound represented by the general formula (1) is replaced by a compound represented by the following general formula (1'): In the formula, Y is an organic group, X, R 1 and R 2 Same meaning as above.
9. The polarizer with an easy-adhesion layer according to claim 7 or 8, wherein The reactive group possessed by the compound represented by the general formula (1) is at least one reactive group selected from the group consisting of a (meth)acrylamide group, an α,β-unsaturated carbonyl group, a vinyl group, a vinyl ether group, an epoxy group, an oxetanyl group, an amino group, an aldehyde group, a mercapto group and a halogen group. 10 . A polarizing film comprising a transparent protective film provided on the easily adhesive layer-formed surface of the polarizer with an easily adhesive layer according to claim 7 , with an adhesive layer interposed therebetween. 11 . An optical film comprising at least one laminate of the polarizing film according to claim 10 . 12 . An image display device using the polarizing film according to claim 10 and / or the optical film according to claim 11.
Citation Information
Patent Citations
JP1973015544B1
JP1975048120A
Method for manufacturing polarizing plate and liquid crystal display device
JP2001296427A
Protective film for polarizer and its manufacturing method
JP2001343529A
Film attached with coating layer, polarizer protecting film and polarization plate using polarizer protecting film
JP2010284840A